Adhesive composition, adhesive layer, and adhesive sheet
Patent Information
- Application Number
- JP2022041796
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-16
- Publication Date
- 2025-03-11
AI Technical Summary
Existing adhesive compositions used in display devices and input devices face challenges in forming effective conductivity paths due to uniform dispersion of antistatic agents, leading to reduced antistatic properties.
The adhesive composition incorporates a sea-island structure with a continuous phase and discontinuous phase, utilizing an ionic compound to form efficient conductivity paths, resulting in a pressure-sensitive adhesive layer with low surface resistivity and excellent antistatic performance.
The solution achieves a pressure-sensitive adhesive layer with low surface resistivity and superior antistatic properties, effectively reducing static electricity generation during application, thereby preventing display defects.
Smart Images

Figure 00000057_0000
Abstract
Description
[Technical Field]
[0001] The present invention relates to an adhesive composition, an adhesive layer, and an adhesive sheet. More specifically, it relates to an adhesive composition, an adhesive layer, and an adhesive sheet that have excellent antistatic properties. [Background technology]
[0002] In recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels have been widely used in various fields. In the manufacturing of these display devices and input devices, adhesive sheets are used to bond optical components. For example, transparent adhesive sheets are used to bond optical components in various display devices such as touch panels.
[0003] In the manufacturing of these display devices and input devices, when an adhesive sheet is attached to the display device, the release liner protecting the adhesive layer is peeled off, generating static electricity in the adhesive layer. This generated static electricity affects the orientation of the display cells in the display device, causing display defects. As a means of suppressing the generation of such static electricity, an antistatic agent is incorporated to reduce the surface resistivity of the adhesive layer (for example, Patent Documents 1-3). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2020-187365 [Patent Document 2] Japanese Patent Publication No. 2019-56115 [Patent Document 3] WO2018 / 008712 publication [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] Because the aforementioned antistatic agent is uniformly dispersed in the adhesive layer, it is difficult to form pathways for imparting conductivity, resulting in a problem of reduced antistatic properties.
[0006] Therefore, the object of the present invention is to provide an adhesive composition that can form an adhesive layer exhibiting low surface resistivity and excellent antistatic performance. Another object of the present invention is to provide an adhesive layer that exhibits low surface resistivity and has excellent antistatic properties. Another object of the present invention is to provide an adhesive sheet having an adhesive layer that exhibits low surface resistivity and has excellent antistatic properties. [Means for solving the problem]
[0007] Therefore, the present inventors conducted diligent studies to solve the above problems and found that in an adhesive composition having a sea-island structure separated into a continuous phase and a discontinuous phase, by including an ionic compound as an antistatic agent in the discontinuous phase, pathways for imparting conductivity can be efficiently formed, resulting in an adhesive layer exhibiting low surface resistivity and excellent antistatic performance. Thus, the present invention was completed.
[0008] In other words, the first aspect of the present invention provides an adhesive composition comprising two or more polymers and an ionic compound, wherein at least one of the two or more polymers is an adhesive polymer (A), and the adhesive composition has a sea-island structure separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) comprises the ionic compound. In this specification, the adhesive composition of the first aspect of the present invention may be referred to as "the adhesive composition of the present invention."
[0009] Furthermore, a second aspect of the present invention provides an adhesive layer formed by the adhesive composition of the present invention. In this specification, the adhesive layer of the second aspect of the present invention may be referred to as "the adhesive layer of the present invention." Furthermore, a third aspect of the present invention provides an adhesive sheet having the adhesive layer of the present invention. In this specification, the adhesive sheet of the third aspect of the present invention may be referred to as "the adhesive sheet of the present invention." Since the adhesive layer and adhesive sheet of the present invention are formed using the adhesive composition of the present invention, they exhibit low surface resistivity and have excellent antistatic properties.
[0010] The adhesive composition of the present invention comprises two or more polymers, at least one of which comprises an adhesive polymer (A). In the adhesive composition of the present invention, the two or more polymers are included as base polymers constituting the adhesive composition of the present invention, and the adhesive polymer (A), which is included as at least one of these polymers, functions as a base polymer that imparts tackiness to the adhesive layer of the present invention.
[0011] The adhesive composition of the present invention contains an ionic compound. In this specification, the ionic compound may be referred to as "the ionic compound of the present invention." In the adhesive composition of the present invention, the ionic compound of the present invention functions as an antistatic agent that imparts conductivity to the adhesive layer of the present invention.
[0012] The adhesive composition of the present invention has a sea-island structure in which a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention. The configuration in which the continuous phase (sea portion) of the adhesive composition of the present invention contains the ionic compound of the present invention is preferable because the ionic compound of the present invention efficiently forms paths for imparting conductivity in the continuous phase, and the adhesive layer of the present invention exhibits a low surface resistivity and has excellent antistatic performance.
[0013] In the adhesive composition of the present invention, the discontinuous phase (island portion) preferably contains the adhesive polymer (A). The configuration in which the discontinuous phase (island portion) contains the adhesive polymer (A) is preferable because it can impart excellent tackiness to the adhesive layer of the present invention without impairing excellent antistatic performance.
[0014] In the adhesive composition of the present invention, the discontinuous phase (island portion) may contain the ionic compound of the present invention. The configuration in which the discontinuous phase (island portion) contains the ionic compound of the present invention is preferable because the adhesive layer of the present invention exhibits an even lower surface resistivity and has excellent antistatic performance.
[0015] In the adhesive composition of the present invention, the ionic compound of the present invention preferably includes an organic compound. The configuration in which the ionic compound of the present invention includes an organic compound is preferable because the adhesive layer of the present invention exhibits an even lower surface resistivity and has excellent antistatic performance.
[0016] In the adhesive composition of the present invention, it is preferable that at least one of the two or more polymers is a conductive polymer (B) that forms a covalent bond with the ionic compound of the present invention. The configuration in which the adhesive composition of the present invention includes a conductive polymer (B) that forms a covalent bond with the ionic compound of the present invention is preferable because it is less likely to cause defects such as corrosion of metal wiring due to the deposition of the ionic compound on the surface of the adhesive layer, and it is possible to suppress the increase in surface resistance in a humid and hot environment and maintain excellent antistatic properties. Furthermore, it is also preferable because it reduces the compatibility between the adhesive layer and the ionic compound, which can prevent defects in transparency and appearance such as clouding, as well as foaming and peeling, especially in a humid and hot environment.
[0017] In the adhesive composition of the present invention, the weight ratio of the conductive polymer (B) to the adhesive polymer (A) (conductive polymer (B) / adhesive polymer (A)) is preferably 10 / 90 to 99 / 1. The configuration in which the weight ratio is 10 / 90 or more is preferable in that the adhesive composition of the present invention can form a sea-island structure in which a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention. Furthermore, the configuration in which the weight ratio is 99 / 1 or less is preferable in that it can impart excellent tackiness to the adhesive layer of the present invention.
[0018] In the adhesive composition of the present invention, it is preferable that the adhesive polymer (A) and the conductive polymer (B) form a block copolymer. This configuration, in which the adhesive polymer (A) and the conductive polymer (B) form a block copolymer, is preferable because the adhesive composition of the present invention can efficiently form a sea-island structure. It is also preferable because the sea-island structure constitutes a microphase separation on the nm scale.
[0019] The thickness of the adhesive sheet of the present invention is preferably 12 to 350 μm. A configuration with a thickness above a certain level is preferable because it makes peeling less likely to occur at stepped areas. A configuration with a thickness below a certain level is preferable because it makes it easier to maintain an excellent appearance during manufacturing. [Effects of the Invention]
[0020] According to the adhesive composition of the present invention, an adhesive layer and adhesive sheet can be obtained that exhibit low surface resistivity and have excellent antistatic performance. [Brief explanation of the drawing]
[0021] [Figure 1] Figure 1 is a schematic diagram (cross-sectional view) showing one embodiment of the adhesive sheet of the present invention. [Modes for carrying out the invention]
[0022] The adhesive composition of the present invention comprises two or more polymers and an ionic compound, wherein at least one of the two or more polymers is an adhesive polymer (A), and has a sea-island structure separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) is an adhesive composition comprising the ionic compound.
[0023] Furthermore, the adhesive layer of the present invention is an adhesive layer formed by the adhesive composition of the present invention. Moreover, the adhesive sheet of the present invention is an adhesive sheet having the adhesive layer of the present invention.
[0024] [1. Adhesive composition] The adhesive composition of the present invention may have any form, for example, solvent type, emulsion type, hot melt type, solvent-free type (active energy ray curing type), etc. In particular, the adhesive composition of the present invention is preferably solvent type or solvent-free type (active energy ray curing type). Solvent-type adhesive compositions are preferred because they can form a stable sea-island structure when an adhesive layer is obtained by heating and / or drying. Solvent-free type (active energy ray curing type) adhesive compositions are also preferred because they can form a stable sea-island structure when an adhesive layer is obtained by irradiation with active energy rays. In this specification, "adhesive composition" means a composition used to form an adhesive layer, and includes the meaning of a composition used to form an adhesive.
[0025] The above-mentioned organic solvent is not particularly limited as long as it is an organic compound used as a solvent, but examples include hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, butanol, and isopropyl alcohol. The above-mentioned organic solvent may also be a mixed solvent containing two or more organic solvents.
[0026] In the adhesive composition of the present invention, two or more polymers are included as base polymers constituting the adhesive composition of the present invention. The number (types) of such polymers is not particularly limited as long as there are two or more, but 2 to 4 types are preferred, 2 or 3 types are more preferred, and 2 types are even more preferred.
[0027] The two or more polymers mentioned above are not particularly limited, but examples include acrylic polymers, rubber polymers, silicone polymers, polyester polymers, urethane polymers, polyamide polymers, epoxy polymers, vinyl alkyl ether polymers, and fluorine polymers. Two or more of these polymers of the same type, or two or more different types, can be used in combination. Among these, acrylic polymers are preferred because of their transparency, weather resistance, adhesive reliability, and the abundance of monomer types, which makes it easy to design solvent-type compositions and solvent-free (active energy ray curing) functional compositions. In other words, the adhesive composition of the present invention is preferably an acrylic adhesive composition containing two or more acrylic polymers as the base polymer.
[0028] The two or more polymers may be composed of at least two polymers bonded to each other by covalent bonds. For example, the two or more polymers may be bonded together by a crosslinking structure using a crosslinking agent, or they may be bonded together by covalent bonds to form, for example, a block copolymer, a graft copolymer, etc. Alternatively, the two or more polymers may be a polymer blend in which no covalent bonds are formed between them.
[0029] The content (total amount) of the two or more polymers in the adhesive composition of the present invention is not particularly limited, but is preferably 75% by weight or more (for example, 75 to 100% by weight), and more preferably 85% by weight or more (for example, 85 to 99.99% by weight).
[0030] [1-1. Adhesive polymer (A)] In the adhesive composition of the present invention, at least one of the two or more polymers is an adhesive polymer (A). The adhesive polymer (A) functions as a base polymer that imparts tackiness to the adhesive layer of the present invention. The adhesive polymer (A) is not particularly limited, but examples include an acrylic polymer contained as a base polymer in an acrylic adhesive composition, a rubber polymer contained as a base polymer in a rubber adhesive composition (such as a natural rubber adhesive composition or a synthetic rubber adhesive composition), a silicone polymer contained as a base polymer in a silicone adhesive composition, a polyester polymer contained as a base polymer in a polyester adhesive composition, a urethane polymer contained as a base polymer in a urethane adhesive composition, a polyamide polymer contained as a base polymer in a polyamide adhesive composition, an epoxy polymer contained as a base polymer in an epoxy adhesive composition, a vinyl alkyl ether polymer contained as a base polymer in a vinyl alkyl ether adhesive composition, and a fluorine polymer contained as a base polymer in a fluorine adhesive composition. Among these, acrylic polymers are preferred as the adhesive polymer (A) due to their transparency, weather resistance, adhesive reliability, and the ease with which solvent-type compositions and solvent-free (active energy ray curing) functional designs can be made due to the wide variety of monomers available. In other words, the adhesive composition of the present invention is preferably an acrylic adhesive composition containing an acrylic polymer as the adhesive polymer (A). The adhesive polymer (A) can be the above-mentioned base polymers used alone or in combination of two or more. In this specification, the acrylic polymer contained as the adhesive polymer (A) may be referred to as "acrylic polymer (A)".
[0031] The content of the adhesive polymer (A) in the adhesive composition of the present invention is not particularly limited, but is preferably 1 to 90% by weight, more preferably 3 to 70% by weight, and even more preferably 5 to 50% by weight. A configuration in which the content of the adhesive polymer (A) is 1% by weight or more is preferable in that it can impart excellent tackiness to the adhesive layer of the present invention. Furthermore, a configuration in which the content of the adhesive polymer (A) is 90% by weight or less is preferable in that the adhesive composition of the present invention can form a sea-island structure in which the phases are separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) contains the ionic compound of the present invention.
[0032] The adhesive composition that forms the adhesive layer containing the acrylic polymer (A) is not particularly limited, but examples include a composition in which the acrylic polymer (A) is an essential component; a composition in which a mixture of monomer components constituting the acrylic polymer (A) (sometimes referred to as a "monomer mixture") or a partially polymer thereof is an essential component. The former is not particularly limited, but examples of the former include so-called solvent-type compositions and water-dispersible compositions (emulsion-type compositions), and examples of the latter include so-called active energy ray-curable compositions. Among these, solvent-type compositions or active energy ray-curable compositions are preferred. The adhesive composition may also contain other additives as needed.
[0033] The term "monomer mixture" as used above includes cases where it is composed of a single monomer component constituting the acrylic polymer (A), and cases where it is composed of two or more monomer components constituting the acrylic polymer (A). Furthermore, the term "partially polymerized product" as used above means a composition in which one or more components of the monomer mixture constituting the acrylic polymer (A) are partially polymerized. In this specification, when "acrylic polymer (A)" is used, unless otherwise specified, it includes "acrylic polymer (A)", "a mixture of monomer components constituting acrylic polymer (A)", and "a partially polymerized mixture of monomer components constituting acrylic polymer (A)".
[0034] Acrylic polymer (A) is a polymer that contains acrylic monomers (acrylic monomers) as essential monomer units (monomer units, monomer constituent units). In other words, acrylic polymer (A) is a polymer that contains constituent units derived from acrylic monomers as constituent units. That is, acrylic polymer (A) is a polymer composed (formed) with acrylic monomers as essential monomer components. In this specification, "(meth)acrylic" refers to either or both of "acrylic" and "methacrylic," and the same applies to other terms. The weight-average molecular weight of acrylic polymer (A) is not particularly limited, but is preferably between 100,000 and 5,000,000.
[0035] The acrylic polymer (A) is preferably a polymer that contains an alkyl (meth)acrylate (hereinafter sometimes simply referred to as "alkyl (meth)acrylate") having a linear or branched alkyl group as an essential monomer unit.
[0036] Examples of the above alkyl (meth)acrylate esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl ((meth)acrylate) (n-butyl (meth)acrylate), isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, ( Examples include alkyl esters of (meth)acrylates having 1 to 20 carbon atoms in the alkyl group, such as nonyl meth)acrylate, isononyl meth)acrylate, decyl meth)acrylate, isodecyl meth)acrylate, undecyl meth)acrylate, dodecyl meth)acrylate, tridecyl meth)acrylate, tetradecyl meth)acrylate, pentadecyl meth)acrylate, hexadecyl meth)acrylate, heptadecyl meth)acrylate, octadecyl meth)acrylate, isostearyl meth)acrylate, nonadecyl meth)acrylate, and eicosyl meth)acrylate. Alkyl meth)acrylates may be used alone or in combination of two or more types.
[0037] In particular, the alkyl (meth)acrylate esters described above are preferred if they have 1 to 18 carbon atoms in the alkyl group, in order to obtain strong adhesion and adjust residual stress, and more preferably methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and isostearyl acrylate (ISTA).
[0038] The content (percentage) of the above alkyl (meth)acrylate in the total monomer units of the acrylic polymer (A) (total amount of monomer components constituting the acrylic polymer (A)) is not particularly limited, but in terms of adhesive reliability, especially adhesive reliability at low temperatures, it is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, and even more preferably 40 to 85 parts by weight, per 100 parts by weight of the total amount of monomer components constituting the acrylic polymer (A).
[0039] Acrylic polymer (A) may contain copolymerizable monomers (copolymerizable monomers) in addition to the above-mentioned alkyl (meth)acrylate as monomer units. In other words, acrylic polymer (A) may contain copolymerizable monomers as constituent monomer components. Note that copolymerizable monomers may be used alone or in combination of two or more types.
[0040] As the copolymerizable monomers mentioned above, carboxyl group-containing monomers are preferred. When the acrylic polymer (A) contains carboxyl group-containing monomers as monomer units, good cohesive force is easily obtained. Therefore, strong adhesion is easily achieved. Furthermore, the carboxyl group can also serve as a reaction site with the crosslinking agent described later.
[0041] The content (ratio) of the carboxyl group-containing monomer relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A) is not particularly limited. The content of the carboxyl group-containing monomer is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight, from the viewpoint of cohesive force, adhesion, ease of obtaining adhesive reliability, and reactivity with crosslinking agents.
[0042] Preferably, the copolymerizable monomers mentioned above are hydroxyl group-containing monomers. When the acrylic polymer (A) contains hydroxyl group-containing monomers as monomer units, polymerization of the constituent monomer components becomes easier, and good cohesive force is easier to obtain. As a result, strong adhesion is easier to obtain, and the gel fraction can be increased, making it easier to obtain excellent foaming resistance and peeling properties. Furthermore, it becomes easier to suppress the whitening of adhesive sheets that may occur in high humidity environments. In addition, the hydroxyl group can also serve as a reaction site with the crosslinking agent described later.
[0043] The content (ratio) of the above-mentioned hydroxyl group-containing monomer relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A) is not particularly limited. When the amount of hydroxyl group-containing monomer is above a certain level, the whitening of the adhesive sheet that may occur in a high-humidity environment can be further suppressed, and transparency such as resistance to humidification-induced clouding can be ensured. The lower limit of the above-mentioned hydroxyl group-containing monomer content is preferably 1 part by weight or more, more preferably 2 parts by weight or more, 3 parts by weight or more, 4 parts by weight or more, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, and even more preferably 10 parts by weight or more. Furthermore, the upper limit of the above-mentioned hydroxyl group-containing monomer content is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, 34 parts by weight or less, 33 parts by weight or less, 32 parts by weight or less, or 31 parts by weight or less, and even more preferably 30 parts by weight or less, from the viewpoint of cohesive force, adhesion, and ease of obtaining adhesive reliability such as resistance to foam peeling.
[0044] Furthermore, nitrogen atom-containing monomers are preferred as the copolymerizable monomers. When the acrylic polymer (A) contains nitrogen atom-containing monomers as monomer units, it becomes easier to obtain appropriate cohesive force. This increases the 180° peel adhesion to glass plates and acrylic plates, making it easier to obtain strong adhesion, and also increases the gel fraction, making it easier to obtain excellent foaming resistance and peeling resistance. In addition, it becomes easier to obtain appropriate flexibility in the adhesive layer, and the 300% tensile residual stress can be adjusted to a specific range, making it easier to obtain excellent stress relaxation and excellent step-following ability.
[0045] The content (ratio) of the nitrogen atom-containing monomer relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A) is not particularly limited, but is preferably 5 parts by weight or more. The lower limit of the nitrogen atom-containing monomer content is preferably 7 parts by weight or more, more preferably 8 parts by weight or more, and even more preferably 9 parts by weight or more, or 10 parts by weight or more, relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A), from the viewpoint of cohesive force, adhesion, and foam peel resistance. Furthermore, the upper limit of the nitrogen atom-containing monomer content is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and even more preferably 30 parts by weight or less, from the viewpoint of making it easier to obtain appropriate flexibility in the adhesive layer and to obtain excellent stress relaxation and excellent step-following properties.
[0046] The above-mentioned acrylic polymer (A) can be obtained by polymerizing the above-mentioned monomer units (monomer components) by known or conventional polymerization methods. Examples of polymerization methods for the above-mentioned acrylic polymer (A) include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by active energy ray irradiation (active energy ray polymerization). Among these, solution polymerization and active energy ray polymerization are preferred in terms of transparency of the adhesive layer, water resistance, and cost, and active energy ray polymerization is more preferred.
[0047] Examples of active energy rays used in the above-mentioned active energy ray polymerization (photopolymerization) include ionizing radiation such as alpha rays, beta rays, gamma rays, neutron rays, and electron beams, as well as ultraviolet rays, with ultraviolet rays being particularly preferred. Furthermore, the irradiation energy, irradiation time, and irradiation method of the active energy rays are not particularly limited, as long as they can activate the photopolymerization initiator and cause a reaction of the monomer components.
[0048] Various common solvents may be used in the polymerization of the above-mentioned acrylic polymer (A). Examples of such solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and organic solvents such as ketones such as methyl ethyl ketone and methyl isobutyl ketone. The solvents may be used individually or in combination of two or more.
[0049] Furthermore, when polymerizing the acrylic polymer (A) described above, polymerization initiators such as thermal polymerization initiators and photopolymerization initiators (photoinitiators) may be used depending on the type of polymerization reaction. The polymerization initiators may be used alone or in combination of two or more types.
[0050] The above-mentioned photopolymerization initiators are not particularly limited, but examples include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and the like. The photopolymerization initiators may be used alone or in combination of two or more.
[0051] Examples of the above-mentioned benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the above-mentioned acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of the above-mentioned α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of the above-mentioned aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of the above-mentioned photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of the above-mentioned benzoin-based photopolymerization initiators include benzoin. Examples of the above-mentioned benzyl-based photopolymerization initiators include benzyl. Examples of the above-mentioned benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. Examples of the above-mentioned ketal-based photopolymerization initiators include benzyldimethylketal. Examples of the above-mentioned thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc.
[0052] The amount of the above-mentioned photopolymerization initiator used is not particularly limited, but for example, it is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.50 parts by weight, per 100 parts by weight of the total monomer units (total amount of monomer components constituting the acrylic polymer (A)) of the acrylic polymer (A).
[0053] Furthermore, the above-mentioned thermal polymerization initiator is not particularly limited, but examples include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. Among these, the azo polymerization initiator disclosed in Japanese Patent Application Publication No. 2002-69411 is preferred. Examples of the above-mentioned azo polymerization initiators include 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid)dimethyl, 4,4'-azobis-4-cyanovaleric acid, etc.
[0054] The amount of the above-mentioned thermal polymerization initiator used is not particularly limited, but for example, in the case of the above-mentioned azo polymerization initiator, it is preferably 0.05 to 0.5 parts by weight, and more preferably 0.1 to 0.3 parts by weight, per 100 parts by weight of the total monomer units (total amount of monomer components constituting the acrylic polymer (A)) of the acrylic polymer (A).
[0055] [1-2. Carboxyl group-containing monomers] The adhesive composition of the present invention preferably contains a carboxyl group-containing monomer as a monomer component constituting the acrylic polymer (A). The inclusion of a carboxyl group-containing monomer as a monomer component constituting the acrylic polymer (A) is preferable because it acts as a reaction site with the crosslinking agent described later, forming a crosslinked structure and efficiently forming the sea-island structure described later. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. Furthermore, the carboxyl group-containing monomer may also include acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride. The carboxyl group-containing monomer may be used alone or in combination of two or more types.
[0056] [1-3. Hydroxyl group-containing monomers] A hydroxyl group-containing monomer refers to a monomer that has at least one hydroxyl group in its molecule. Furthermore, a monomer that has at least one hydroxyl group and at least one carboxyl group in its molecule is a carboxyl group-containing monomer and not a hydroxyl group-containing monomer. The above hydroxyl group-containing monomers are not particularly limited, but specifically include, for example, hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl) (meth)acrylate; vinyl alcohol, allyl alcohol, etc. Among these, hydroxyl group-containing monomers are preferably hydroxyl group-containing (meth)acrylic acid esters, and more preferably 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl (meth)acrylate (HPA), and 4-hydroxybutyl acrylate (4HBA). The hydroxyl group-containing monomers may be used alone or in combination of two or more.
[0057] [1-4. Nitrogen atom-containing monomers] A nitrogen atom-containing monomer refers to a monomer that has at least one nitrogen atom within its molecule (one molecule). However, the above-mentioned hydroxyl group-containing monomer does not include nitrogen atom-containing monomers. In other words, in this specification, monomers having both a hydroxyl group and a nitrogen atom in their molecule are included in nitrogen atom-containing monomers. Furthermore, a monomer having at least one nitrogen atom and at least one carboxyl group in its molecule is a carboxyl group-containing monomer and not a nitrogen atom-containing monomer.
[0058] From the viewpoint of improving foam peeling resistance, N-vinylcyclic amides, (meth)acrylamides, heterocyclic monomers, etc., are preferred as the nitrogen atom-containing monomers. The nitrogen atom-containing monomers may be used alone or in combination of two or more.
[0059] Examples of the heterocyclic monomers mentioned above include (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, and N-methylvinylpyrrolidone.
[0060] Examples of the above N-vinylcyclic amides include N-vinylcyclic amides represented by the following formula (1). [ka] (In formula (1), R 1 (This indicates a divalent organic group.)
[0061] R in equation (1) above 1The group is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).
[0062] From the viewpoint of further improving foam peel resistance, the N-vinyl cyclic amide represented by formula (1) above is preferably N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholindione, more preferably N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and even more preferably N-vinyl-2-pyrrolidone.
[0063] Examples of the above (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, and N,N-dialkyl(meth)acrylamide. Examples of the above N-alkyl(meth)acrylamide include N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, and N-octylacrylamide. Furthermore, the above N-alkyl(meth)acrylamide also includes (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Examples of the above N,N-dialkyl(meth)acrylamide include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.
[0064] Furthermore, the above-mentioned (meth)acrylamides also include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the above-mentioned N-hydroxyalkyl (meth)acrylamides include N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, and N-methyl-N-2-hydroxyethyl(meth)acrylamide.
[0065] Furthermore, the above-mentioned (meth)acrylamides also include, for example, various N-alkoxyalkyl(meth)acrylamides. Examples of the above-mentioned N-alkoxyalkyl(meth)acrylamides include N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide.
[0066] Furthermore, nitrogen atom-containing monomers other than the above heterocyclic monomers, N-vinylcyclic amides, and (meth)acrylamides include, for example, amino group-containing monomers such as (meth)aminoethyl acrylate, (meth)dimethylaminoethyl acrylate, (meth)dimethylaminopropyl acrylate, and (meth)butylaminoethyl acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide; and N-ethyl Examples include itaconimide monomers such as itaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; imide group-containing monomers such as succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate.
[0067] As nitrogen atom-containing monomers, heterocyclic monomers are preferred in terms of cohesive force, adhesion, and resistance to foam peeling, and (meth)acryloylmorpholine is preferred.
[0068] [1-5. (Meth)acrylate alkoxyalkyl esters] Besides carboxyl group-containing monomers, nitrogen atom-containing monomers, and hydroxyl group-containing monomers, other copolymerizable monomers include (meth)acrylate alkoxyalkyl esters having linear or branched alkoxyalkyl groups (hereinafter sometimes simply referred to as "(meth)acrylate alkoxyalkyl esters"). (Meth)acrylate alkoxyalkyl esters can be used alone or in combination of two or more types.
[0069] Examples of the above-mentioned (meth)acrylate alkoxyalkyl esters include (meth)acrylate alkyl esters having an alkoxyalkyl group in which an alkoxy group having 1 to 20 carbon atoms is substituted with an alkyl group having 1 to 20 carbon atoms, such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. Note that (meth)alkoxyacrylate alkyl esters may be used alone or in combination of two or more types.
[0070] In particular, among the above-mentioned (meth)acrylate alkoxyalkyl esters, those in which the alkoxy group having 1 to 18 carbon atoms is substituted with an alkyl group having 1 to 18 carbon atoms are preferred, and more preferably 2-methoxyethyl acrylate (MEA), in terms of obtaining strong adhesion and adjusting residual stress.
[0071] The content (percentage) of the above-mentioned (meth)acrylate alkoxyalkyl ester in the total monomer units of the acrylic polymer (A) (total amount of monomer components constituting the acrylic polymer (A)) is not particularly limited, but in terms of adhesive reliability, especially adhesive reliability at low temperatures, it is preferably 30 to 100 parts by weight, more preferably 35 to 90 parts by weight, and even more preferably 40 to 85 parts by weight, per 100 parts by weight of the total amount of monomer components constituting the acrylic polymer (A).
[0072] [1-6. Monomers containing alicyclic structures] Besides carboxyl group-containing monomers, nitrogen atom-containing monomers, and hydroxyl group-containing monomers, copolymerizable monomers other than alicyclic structure-containing monomers can be included. The above alicyclic structure-containing monomers are not particularly limited as long as they have polymerizable functional groups having unsaturated double bonds, such as (meth)acryloyl groups or vinyl groups, and have an alicyclic structure. For example, alkyl (meth)acrylates having cycloalkyl groups are included in the above alicyclic structure-containing monomers. Alicyclic structure-containing monomers can be used alone or in combination of two or more types.
[0073] The alicyclic structure in the above-mentioned alicyclic structure-containing monomer is a cyclic hydrocarbon structure, preferably having 5 or more carbon atoms, more preferably 6 to 24 carbon atoms, even more preferably 6 to 15 carbon atoms, and particularly preferably 6 to 10 carbon atoms.
[0074] Examples of monomers containing the above-mentioned alicyclic structure include (meth)acrylic monomers such as cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, HPMPA represented by formula (2) below, TMA-2 represented by formula (3) below, and HCPA represented by formula (4) below. In formula (4) below, the bond site between the cyclohexyl ring connected by a line and the structural formula in parentheses is not particularly limited. Among these, isobornyl (meth)acrylate is preferred. [ka] [ka] [ka]
[0075] When the acrylic polymer (A) contains the above-mentioned alicyclic structure-containing monomer as a monomer component constituting the polymer, the proportion of the above-mentioned alicyclic structure-containing monomer in the total monomer components (100% by weight) constituting the acrylic polymer (A) is not particularly limited, but is preferably 10% by weight or more from the viewpoint of improving durability and obtaining high adhesive reliability. Furthermore, the upper limit of the proportion of the above-mentioned alicyclic structure-containing monomer is preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less from the viewpoint of obtaining an adhesive layer with appropriate flexibility.
[0076] [1-7. Other copolymerizable monomers] Examples of copolymerizable monomers in acrylic polymer (A) include, in addition to the carboxyl group-containing monomers, nitrogen atom-containing monomers, and hydroxyl group-containing monomers mentioned above, epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [e.g., sodium vinyl sulfonate, etc.]; phosphate group-containing monomers; (meth)acrylic acid esters having aromatic hydrocarbon groups [e.g., phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [e.g., vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [e.g., styrene, vinyltoluene, etc.]; olefins or dienes [e.g., ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [e.g., vinyl alkyl ether, etc.]; vinyl chloride, etc.
[0077] Furthermore, polyfunctional monomers can also be used as copolymerizable monomers in the above-mentioned acrylic polymer (A). Polyfunctional monomers act as crosslinking components. Examples of the above-mentioned polyfunctional monomers include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, etc. Polyfunctional monomers may be used alone or in combination of two or more types.
[0078] The content (percentage) of the polyfunctional monomer in the total monomer units of the acrylic polymer (A) is not particularly limited, but is preferably 0.5 parts by weight or less (for example, 0 to 0.5 parts by weight), more preferably 0 to 0.35 parts by weight, and even more preferably 0 to 0.3 parts by weight, relative to the total amount (100 parts by weight) of monomer components constituting the acrylic polymer (A). When the polyfunctional monomer content is 0.5 parts by weight or less, the adhesive layer has appropriate cohesive force, which is preferable as it easily improves adhesive strength and step absorption. When a crosslinking agent is used, the polyfunctional monomer may not be used, but when a crosslinking agent is not used, the polyfunctional monomer content is preferably 0.001 to 0.5 parts by weight, more preferably 0.001 to 0.35 parts by weight, and even more preferably 0.002 to 0.3 parts by weight.
[0079] [1-8. Acrylic polymers (B)] When the adhesive of the present invention contains an acrylic polymer (A) as a base polymer, it is preferable that the adhesive composition of the present invention contains, together with the acrylic polymer (A), an acrylic polymer (B) having a weight-average molecular weight of 1,000 to 30,000 as an adhesive polymer. The inclusion of acrylic polymer (B) improves the adhesion to the adherend at the interface of the adhesive sheet, making it easier to obtain strong adhesion and excellent foaming resistance. In this specification, "acrylic polymer (B) having a weight-average molecular weight of 1,000 to 30,000" may be simply referred to as "acrylic polymer (B)".
[0080] As the above acrylic polymer (B), an acrylic polymer composed of (meth)acrylic acid ester having a cyclic structure in the molecule as an essential monomer component is preferred, and an acrylic polymer composed of (meth)acrylic acid ester having a cyclic structure in the molecule and (meth)acrylic acid alkyl ester having a linear or branched alkyl group as essential monomer components is preferred. In other words, as the above acrylic polymer (B), an acrylic polymer containing (meth)acrylic acid ester having a cyclic structure in the molecule as a monomer unit is preferred, and an acrylic polymer containing (meth)acrylic acid ester having a cyclic structure in the molecule and (meth)acrylic acid alkyl ester having a linear or branched alkyl group as a monomer unit is preferred.
[0081] The cyclic structure (ring) of the above-mentioned (meth)acrylic acid ester having a cyclic structure within the molecule (within one molecule) (hereinafter sometimes referred to as "ring-containing (meth)acrylic acid ester") may be either an aromatic ring or a non-aromatic ring, and is not particularly limited. Examples of the aromatic ring include aromatic carbocyclic rings [for example, monocyclic carbocyclic rings such as benzene rings, or fused carbocyclic rings such as naphthalene rings], and various aromatic heterocyclic rings. Examples of the above-mentioned non-aromatic rings include non-aromatic aliphatic rings (non-aromatic alicyclic rings) [e.g., cycloalkane rings such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane rings; cycloalkene rings such as cyclohexene rings, etc.], non-aromatic bridged rings [e.g., bicyclic hydrocarbon rings in pinane, pinene, bornane, norbornane, norbornene, etc.; triplicate or more aliphatic hydrocarbon rings (bridged hydrocarbon rings) in adamantane, etc.], and non-aromatic heterocycles [e.g., epoxy rings, oxolane rings, oxetane rings, etc.].
[0082] Examples of the above-mentioned aliphatic hydrocarbon rings with three or more rings (cross-linked hydrocarbon rings with three or more rings) include the dicyclopentanyl group represented by formula (5a), the dicyclopentenyl group represented by formula (5b), the adamantyl group represented by formula (5c), the tricyclopentanyl group represented by formula (5d), and the tricyclopentenyl group represented by formula (5e). [ka]
[0083] In other words, the above-mentioned ring-containing (meth)acrylic acid esters include, for example, cycloalkyl (meth)acrylic acid esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, and 1-adamantine Examples include (meth)acrylic acid esters having three or more aliphatic hydrocarbon rings, such as phthal(meth)acrylate, 2-methyl-2-adamantyl(meth)acrylate, and 2-ethyl-2-adamantyl(meth)acrylate; and (meth)acrylic acid esters having aromatic rings, such as aryl (meth)acrylate esters like phenyl(meth)acrylate, aryloxyalkyl (meth)acrylate esters like phenoxyethyl(meth)acrylate, and arylalkyl (meth)acrylate esters like benzyl(meth)acrylate. Among these, non-aromatic ring-containing (meth)acrylic acid esters are particularly preferred as the above ring-containing (meth)acrylic acid esters, more preferably cyclohexyl acrylate (CHA), cyclohexyl methacrylate (CHMA), dicyclopentanyl acrylate (DCPA), and dicyclopentanyl methacrylate (DCPMA), and even more preferably dicyclopentanyl acrylate (DCPA) and dicyclopentanyl methacrylate (DCPMA). Furthermore, ring-containing (meth)acrylic acid esters may be used alone or in combination of two or more types.
[0084] Among the non-aromatic ring-containing (meth)acrylic acid esters mentioned above, (meth)acrylic acid esters having three or more aliphatic hydrocarbon rings (especially three or more cross-linked hydrocarbon rings) are particularly preferred because they are less likely to inhibit polymerization. Furthermore, when (meth)acrylic acid esters having a dicyclopentanyl group represented by formula (5a), an adamantyl group represented by formula (5c), or a tricyclopentanyl group represented by formula (5d) that do not have an unsaturated bond are used, foam peel resistance can be further improved, and adhesion to low-polarity substrates such as polyethylene and polypropylene can be significantly improved.
[0085] The content (percentage) of the above-mentioned ring-containing (meth)acrylic acid ester in the total monomer units of the acrylic polymer (B) (total amount of monomer components constituting the acrylic polymer (B)) is not particularly limited, but is preferably 10 to 90 parts by weight, and more preferably 20 to 80 parts by weight, based on the total amount of monomer components constituting the acrylic polymer (B) (100 parts by weight). A content of 10 parts by weight or more of the above-mentioned ring-containing (meth)acrylic acid ester is preferable because it tends to improve foam peel resistance. Furthermore, a content of 90 parts by weight or less is preferable because the adhesive layer has appropriate flexibility, which tends to improve adhesive strength and step absorption.
[0086] Furthermore, examples of alkyl (meth)acrylate esters having the above-mentioned linear or branched alkyl group as monomer units of the acrylic polymer (B) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and 2-ethyl (meth)acrylate. Examples include alkyl esters of (meth)acrylates having 1 to 20 carbon atoms in the alkyl group, such as hexyl, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, methyl methacrylate (MMA) is preferred because it has good compatibility with acrylic polymer (A). The above alkyl esters of (meth)acrylates may be used alone or in combination of two or more.
[0087] The content (percentage) of the alkyl (meth)acrylate having the linear or branched alkyl group in the total monomer units of the acrylic polymer (B) (the total amount of monomer components constituting the acrylic polymer (B)) is not particularly limited, but in terms of resistance to foaming and peeling, it is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight, per 100 parts by weight of the total amount of monomer components constituting the acrylic polymer (B). A content of 10 parts by weight or more is particularly preferable because it tends to improve adhesion to substrates made of acrylic resin or polycarbonate.
[0088] In addition to the ring-containing (meth)acrylic acid esters and alkyl (meth)acrylic acid esters having linear or branched alkyl groups, the monomer units of the acrylic polymer (B) may also include monomers that can copolymerize with these monomers (copolymerizable monomers). The content (percentage) of the copolymerizable monomers in the total monomer units of the acrylic polymer (B) (total amount of monomer components constituting the acrylic polymer (B)) is not particularly limited, but is preferably 49.9 parts by weight or less (for example, 0 to 49.9 parts by weight) and more preferably 30 parts by weight or less, based on the total amount of monomer components constituting the acrylic polymer (B) (100 parts by weight). Furthermore, copolymerizable monomers may be used alone or in combination of two or more types.
[0089] Examples of copolymerizable monomers as monomer units of acrylic polymer (B) include (meth)acrylate alkoxyalkyl esters [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.]; hydroxyl group-containing monomers [e.g., 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc., hydroxyalkyl (meth)acrylate, vinyl alcohol, etc.]; hydroxyl group-containing monomers [e.g., 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc., hydroxyalkyl (meth)acrylate, vinyl alcohol, etc.] Examples include: allyl alcohol, etc.; amide group-containing monomers [e.g., (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, etc.]; amino group-containing monomers [e.g., aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate, etc.]; cyano group-containing monomers [e.g., acrylonitrile, methacrylonitrile, etc.]; sulfonic acid group-containing monomers [e.g., sodium vinylsulfonate, etc.]; phosphate group-containing monomers [e.g., 2-hydroxyethylacryloylphosphate, etc.]; isocyanate group-containing monomers [e.g., 2-methacryloyloxyethyl isocyanate, etc.]; imide group-containing monomers [e.g., cyclohexylmaleimide, isopropylmaleimide, etc.], etc.
[0090] As described above, the acrylic polymer (B) is preferably an acrylic polymer containing a (meth)acrylic acid ester having a cyclic structure within the molecule and an alkyl (meth)acrylic acid ester having a linear or branched alkyl group as monomer units. In particular, it is preferable that the acrylic polymer contains a ring-containing (meth)acrylic acid ester and the alkyl (meth)acrylic acid ester having the linear or branched alkyl group as monomer units. In the acrylic polymer containing a ring-containing (meth)acrylic acid ester and an alkyl (meth)acrylic acid ester having a linear or branched alkyl group as monomer units, the amount of ring-containing (meth)acrylic acid ester relative to the total amount of monomer components constituting the acrylic polymer (B) (100 parts by weight) is not particularly limited, but is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight. Furthermore, the content of alkyl (meth)acrylic acid ester having a linear or branched alkyl group is not particularly limited, but is preferably 10 to 90 parts by weight, more preferably 20 to 80 parts by weight, and even more preferably 20 to 60 parts by weight.
[0091] Furthermore, a particularly preferred specific configuration of the acrylic polymer (B) is an acrylic polymer containing (1) at least one monomer selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and (2) methyl methacrylate as monomer units. In the acrylic polymer (B) with the above particularly preferred specific configuration, the content of (1) dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate (the total amount if two or more are included) in the total monomer units of the acrylic polymer (B) is preferably 30 to 70 parts by weight, and the content of (2) methyl methacrylate is preferably 30 to 70 parts by weight, relative to the total amount of monomer components constituting the acrylic polymer (B) (100 parts by weight). However, the acrylic polymer (B) is not limited to the above specific configuration.
[0092] Acrylic polymer (B) can be obtained by polymerizing the above monomer components by known or conventional polymerization methods. Examples of polymerization methods for acrylic polymer (B) include solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by active energy ray irradiation (active energy ray polymerization). Among these, bulk polymerization and solution polymerization are preferred, and solution polymerization is more preferred.
[0093] Various common solvents may be used in the polymerization of the acrylic polymer (B). Examples of such solvents include esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and organic solvents such as ketones such as methyl ethyl ketone and methyl isobutyl ketone. These solvents may be used individually or in combination of two or more.
[0094] Furthermore, known or conventional polymerization initiators (e.g., thermal polymerization initiators or photopolymerization initiators) may be used during the polymerization of the acrylic polymer (B). The polymerization initiator may be used alone or in combination of two or more types.
[0095] Examples of thermal polymerization initiators include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis-2-methylbutyronitrile (AMBN), 2,2'-azobis(2-methylpropionic acid)dimethyl, 4,4'-azobis-4-cyanovaleric acid, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 1,1'-azobis(cyclohexane-1- Examples of azo initiators include carbonitrine, 2,2'-azobis(2,4,4-trimethylpentane), and peroxide initiators such as benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(t-butylperoxy)cyclododecane. When performing solution polymerization, it is preferable to use an oil-soluble polymerization initiator. Furthermore, thermal polymerization initiators may be used alone or in combination of two or more.
[0096] The amount of thermal polymerization initiator used is not particularly limited, but for example, it is 0.1 to 15 parts by weight per 100 parts by weight of the total monomer units of the acrylic polymer (B) (total amount of monomer components constituting the acrylic polymer (B)).
[0097] Furthermore, the above-mentioned photopolymerization initiator is not particularly limited, but for example, the same photopolymerization initiator used in the polymerization of the acrylic polymer (A) mentioned above can be used. The amount of the above-mentioned photopolymerization initiator used is not particularly limited and can be selected as appropriate.
[0098] In polymerization of the above-mentioned acrylic polymer (B), a chain transfer agent may be used to adjust the molecular weight (specifically, to adjust the weight-average molecular weight to 1,000 to 30,000). Examples of such chain transfer agents include 2-mercaptoethanol, α-thioglycerol, 2,3-dimercapto-1-propanol, octyl mercaptan, t-nonyl mercaptan, dodecyl mercaptan (lauryl mercaptan), t-dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, t-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, thioglycolic acid ester of ethylene glycol, thioglycolic acid ester of neopentyl glycol, thioglycolic acid ester of pentaerythritol, α-methylstyrene dimer, and the like. In particular, α-thioglycerol and methyl thioglycolate are preferred, with α-thioglycerol being especially preferred, from the viewpoint of suppressing whitening of the adhesive sheet due to humidification. The chain transfer agent may be used alone or in combination of two or more types.
[0099] The content (amount used) of the above-mentioned chain transfer agent is not particularly limited, but is preferably 0.1 to 20 parts by weight, more preferably 0.2 to 15 parts by weight, and even more preferably 0.3 to 10 parts by weight, per 100 parts by weight of the total monomer units (total amount of monomer components constituting the acrylic polymer (B)) of the acrylic polymer (B). By setting the content (amount used) of the chain transfer agent within the above range, an acrylic polymer with a weight-average molecular weight controlled to 1000 to 30000 can be easily obtained.
[0100] The weight-average molecular weight (Mw) of the above acrylic polymer (B) is 1,000 to 30,000, preferably 1,000 to 20,000, more preferably 1,500 to 10,000, and even more preferably 2,000 to 8,000. Since the weight-average molecular weight of the acrylic polymer (B) is 1,000 or more, adhesive strength and retention properties are improved, and foam peel resistance is enhanced. On the other hand, since the weight-average molecular weight of the acrylic polymer (B) is 30,000 or less, it is easier to increase adhesive strength and foam peel resistance is enhanced.
[0101] The weight-average molecular weight (Mw) of the above acrylic polymer (B) can be determined by converting it to polystyrene equivalent using the GPC method. For example, it can be measured using the high-speed GPC instrument "HPLC-8120GPC" manufactured by Tosoh Corporation under the following conditions. Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000 Solvent: tetrahydrofuran Flow rate: 0.6ml / min
[0102] The glass transition temperature (Tg) of the acrylic polymer (B) is not particularly limited, but is preferably 20 to 300°C, more preferably 30 to 300°C, and even more preferably 40 to 300°C. A glass transition temperature of 20°C or higher for the acrylic polymer (B) is preferable because it easily improves foam peel resistance. Furthermore, a glass transition temperature of 300°C or lower for the acrylic polymer (B) is preferable because the adhesive layer has appropriate flexibility, making it easier to obtain good adhesive strength and good step absorption, and thus easier to obtain excellent adhesive reliability.
[0103] The glass transition temperature (Tg) of the above acrylic polymer (B) is the theoretical glass transition temperature expressed by the following formula. 1 / Tg = W1 / Tg1 + W2 / Tg2 + ... + W n / Tg n In the above formula, Tg is the glass transition temperature (unit: K) of the acrylic polymer (B), Tg i This is the glass transition temperature (unit: K) when monomer i forms a homopolymer, Wi represents the weight fraction of monomer i in the total amount of monomer components (i = 1, 2, .... n). For the Tg of the monomer homopolymer constituting the above acrylic polymer (B), the values listed in Table 1 below can be used. For monomer homopolymers not listed in Table 1, the values listed in "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989) can be used. Furthermore, for monomer homopolymers not listed in the above literature, the values obtained by the measurement method described above (tanδ peak top temperature by viscoelasticity test) can be used.
[0104] [Table 1] Note that in Table 1, the copolymer "DCPMA / MMA=60 / 40" refers to a copolymer consisting of 60 parts by weight of DCPMA and 40 parts by weight of MMA.
[0105] When the adhesive composition of the present invention contains acrylic polymers (A) and (B), the content of acrylic polymer (B) is not particularly limited, but is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, per 100 parts by weight of acrylic polymer (A). That is, the content of acrylic polymer (B) in the adhesive composition of the present invention is not particularly limited, but is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, per 100 parts by weight of the total monomer units of acrylic polymer (A). The content of acrylic polymer (B) in the adhesive composition of the present invention is not particularly limited, but for example, is preferably 1 to 30 parts by weight, more preferably 2 to 20 parts by weight, and even more preferably 2 to 10 parts by weight, per 100 parts by weight of the monomer mixture. When the content of acrylic polymer (B) is 1 part by weight or more, it is easier to obtain excellent adhesion and excellent foaming resistance, which is preferable. Furthermore, it is preferable that the acrylic polymer (B) content is 30 parts by weight or less, as this makes it easier to obtain excellent transparency and adhesive reliability.
[0106] The method for preparing the adhesive composition containing acrylic polymers (A) and (B) is not particularly limited. For example, it can be prepared by adding acrylic polymer (B), additives, etc., as needed to a mixture of monomer components constituting acrylic polymer (A) or a partially polymerized mixture of monomer components constituting acrylic polymer (A) (a monomer mixture that forms acrylic polymer (A) or a partially polymer thereof), and then mixing.
[0107] [1-9. Ionic Compounds of the Present Invention] The adhesive composition of the present invention contains the ionic compound of the present invention as an essential component. In the adhesive composition of the present invention, the ionic compound of the present invention functions as an antistatic agent that imparts conductivity to the adhesive layer of the present invention. The ionic compound of the present invention is liquid (liquid state) at any temperature within the range of 0 to 150°C, is a non-volatile molten salt, and is preferably transparent (ionic liquid). The ionic compound of the present invention can be used alone or in combination of two or more types.
[0108] The ionic compound of the present invention is not particularly limited, but organic compounds (organic ionic compounds) are preferred.
[0109] As the above-mentioned organic ionic compound, an organic cation anion salt can be preferably used. In this invention, "organic cation anion salt" refers to an organic salt in which the cation portion is composed of an organic substance, and the anion portion may be an organic substance or an inorganic substance. "Organic cation anion salt" is also called an ionic liquid or an ionic solid. Furthermore, as the anion component constituting the ionic compound, it is preferable to use a fluorine-containing anion from the viewpoint of antistatic function. Ionic compounds can be used alone or in combination of multiple compounds.
[0110] The organic cation anion salt is composed of a cation component and an anion component, and the cation component is composed of organic substances. Specifically, examples of the cation component include pyridinium cation, piperidinium cation, pyrrolidinium cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazolium cation, tetrahydropyrimidinium cation, dihydropyrimidinium cation, pyrazolium cation, pyrazolinium cation, tetraalkylammonium cation, trialkylsulfonium cation, tetraalkylphosphonium cation, and the like.
[0111] Examples of the anion component include, for example, Cl - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO 2 )3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (CN)2N - , C4F9SO3 - , C3F7COO - , ((CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - , and the following general formulas (1) to (4), (1):(C n F 2n+1 SO2)2N - (where n is an integer from 1 to 10), (2):CF2(C<- O3S(CF2) l SO3 - (where l is an integer between 1 and 10) (4):(C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (where p and q are integers from 1 to 10), and (FSO2)2N - The following are used. Among them, anions containing a fluorine atom (fluorine-containing anions) are particularly preferred because they yield ionic compounds with good ionic dissociation properties. Among anions containing a fluorine atom, fluorine-containing imide anions are preferred, and among these, bis(trifluoromethanesulfonyl)imide anions and bis(fluorosulfonyl)imide anions are particularly preferred. In particular, bis(fluorosulfonyl)imide anions are preferred because they can impart excellent antistatic properties with relatively small additions, maintain adhesive properties, and are advantageous for durability in humid and heated environments.
[0112] The ionic compound of the present invention is preferably an ionic compound (hereinafter referred to as "ionic compound (A)") having a functional group (hereinafter sometimes referred to as "functional group (A)" in this specification) that can form a covalent bond with at least one of the two or more polymers constituting the adhesive composition of the present invention, in the cation portion and / or the anion portion (either or both) constituting the ionic compound.
[0113] The adhesive composition of the present invention contains an ionic compound (A), which causes at least one of two or more polymers to react with the functional group (A) of the ionic compound (A) to form a covalent bond, thereby incorporating the ionic compound into the polymer molecule. As a result, compatibility in the adhesive layer of the present invention is not impaired, and transparency is easily maintained. Furthermore, it is preferable because it can suppress the bleed-out of the antistatic component even under harsh conditions such as humid and hot environments, making defects such as corrosion of metal wiring less likely to occur, and it can suppress the increase in surface resistance under humid and hot environments, thereby maintaining excellent antistatic properties. In addition, precipitation, foaming, and peeling on the surface of the adhesive layer are suppressed, making defects in durability such as appearance and adhesive reliability less likely to occur.
[0114] The cation portion of the ionic compound (A) can be used without particular limitations, but examples include quaternary ammonium cations, imidazolium cations, pyridinium cations, piperinidinium cations, pyrrolidinium cations, quaternary phosphonium cations, trialkylsulfonium cations, pyrrole cations, pyrazolium cations, guanidium cations, etc. Among these, the use of quaternary ammonium cations, imidazolium cations, pyridinium cations, piperinidinium cations, pyrrolidinium cations, quaternary phosphonium cations, and trialkylsulfonium cations is more preferred.
[0115] Furthermore, among the anion portion constituting the ionic compound (A), the anion is SCN. - BF4 - PF6 - NO3 - CH3COO - CF3COO - CH3SO3 - CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - (CF3SO2) 3 C - AsF6 - SbF6 - , NbF6 - TaF6- , F(HF) n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - C3F7COO - (CF3SO2)(CF3CO)N - , B(CN)4 - , C(CN)3 - , N(CN)2 - CH3OSO3 - ,C2H5OSO3 - , C4H9OSO3 - , C6H 13 OSO3 - C8H 17 OSO3 - p-toluenesulfonate anion, 2-(2-methoxyethyl)ethyl sulfate anion, (C2F5)3PF3 - These are some examples, and in particular, anionic components containing fluorine atoms (fluorine-containing anions) are preferred because they yield ionic compounds with low melting points and have excellent antistatic properties. However, it is preferable not to use chloride ions, bromide ions, etc., as anions because they are corrosive.
[0116] Examples of functional groups (A) (functional groups that can form covalent bonds with the polymer) that the ionic compound (A) possesses include (meth)acryloyloxy groups, (meth)acryloylamino groups, vinyl groups, allyl groups, styryl groups, hydroxyl groups, amino groups, mercapto groups, epoxy groups, etc. Among these, (meth)acryloyloxy groups, (meth)acryloylamino groups, and hydroxyl groups are preferred, and particularly preferred is a (meth)acryloyloxy group that can copolymerize with the polymer. In addition, amino groups also include -NH2 and -NHR (where R is an alkyl group having 1 to 6 carbon atoms).
[0117] The number of functional groups (A) possessed by the ionic compound (A) is not particularly limited, but 1 to 4 are preferred, 1 to 3 are more preferred, 1 or 2 are even more preferred, and 1 is particularly preferred. When the number of functional groups (A) is 2 or more, the two or more functional groups (A) may be the same or different. In addition, when the number of functional groups (A) is 2 or more, the ionic compound (A) can also function as a crosslinking agent for crosslinking two or more polymers.
[0118] As the ionic compound (A), it can be used without particular limitation, but it is preferably an ionic compound represented by the following general formula (A).
Chemical formula
[0119] In the above general formula (A), X + is the cationic part. Y - is an anion. Z 1 and Z 2 are the same or different and are a single bond or an alkylene group having 1 to 16 carbon atoms. A 1 and A 2 are the same or different and are functional groups capable of forming a covalent bond with the acrylic polymer (A). n 1 is 0 or 1, n 2 is 0 or 1, provided that n 1 [[ID=3,2]]+ n 2 is 1 or 2.
[0120] Examples of the cationic part (X + ) constituting the ionic compound represented by the above general formula (A) include a quaternary ammonium group, an imidazolium group, a pyridinium group, a piperidinidinium group, a pyrrolidinium group, a pyrrole group, a quaternary phosphonium group, a trialkylsulfonium group, a pyrazolium group, a guanidinium group, and the like. Among these, in particular, a quaternary ammonium group is a preferred embodiment in terms of excellent transparency and being suitable for electronic and optical applications. In addition, it is presumed that the quaternary ammonium group is less likely to inhibit a general radical polymerization reaction during ultraviolet (UV) curing and has high curability, and is suitable.
[0121] As for the quaternary ammonium group, when n 1 + n 2 is 1, examples include trimethylammonium group, triethylammonium group, tripropylammonium group, methyldiethylammonium group, ethyldimethylammonium group, methyldipropylammonium group, dimethylbenzylammonium group, diethylbenzylammonium group, methyldibenzylammonium group, ethyldibenzylammonium group, dimethyloctadecylammonium group, dimethyloleylammonium group, etc. Among them, particularly, the trimethylammonium group and the dimethylbenzylammonium group are preferred embodiments in terms of the easy availability of inexpensive industrial materials.
[0122] As for the quaternary ammonium group, when n 1 + n 2 is 2, examples include dimethylammonium group, diethylammonium group, dipropylammonium group, methylethylammonium group, methylpropylammonium group, methylbenzylammonium group, ethylbenzylammonium group, methyloctadecylammonium group, ethyloctadecylammonium group, methyloleylammonium, ethyloleylammonium group, etc. Among them, particularly, the dimethylammonium group and the methyloleylammonium group are preferred embodiments in terms of the easy availability of inexpensive industrial materials.
[0123] Within the anion (site) (Y - ) that constitutes the ionic compound represented by the above general formula (A), as the anion, SCN - , BF4 - , PF6 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (FSO2)2N - , (CF3SO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6- , NbF6 - TaF6 - , F(HF) n - , (CN)2N - , C4F9SO3 - , (C2F5SO2)2N - C3F7COO - (CF3SO2)(CF3CO)N - , B(CN)4 - , C(CN)3 - , N(CN)2 - CH3OSO3 - ,C2H5OSO3 - , C4H9OSO3 - , C6H 13 OSO3 - C8H 17 OSO3 - p-toluenesulfonate anion, 2-(2-methoxyethyl)ethyl sulfate anion, (C2F5)3PF3 - These are some examples, and in particular, anionic components containing fluorine atoms (fluorine-containing anions) are preferred because they yield ionic compounds with low melting points and have excellent antistatic properties. However, it is preferable not to use chloride ions, bromide ions, etc., as anions because they are corrosive.
[0124] The ionic compound represented by the general formula (A) above contains Z 1 and Z 2 This is a single bond or an alkylene group having 1 to 16 carbon atoms. Preferably, the alkylene group having 1 to 12 carbon atoms is preferred, more preferably an alkylene group having 1 to 6 carbon atoms is preferred, and particularly preferably an alkylene group having 1 to 3 carbon atoms is preferred. Specifically, examples include a methylene group, an ethylene group, a trimethylene group, and a methylethylene group, with ethylene and trimethylene groups being preferred. 1 +n 2 If Z is 2, 1 and Z 2 They may be the same or they may be different.
[0125] A constitutes the ionic compound represented by the above general formula (A).1 and A 2 This refers to a functional group that can form a covalent bond with the acrylic polymer (A), specifically including (meth)acryloyloxy group, (meth)acryloylamino group, vinyl group, allyl group, styryl group, hydroxyl group, amino group, mercapto group, epoxy group, etc. Among these, (meth)acryloyloxy group, (meth)acryloylamino group, and hydroxyl group are preferred, and particularly preferred is a (meth)acryloyloxy group that can copolymerize with the acrylic polymer (A). 1 +n 2 If A is 2, 1 and A 2 They may be the same or they may be different.
[0126] Among the ionic compounds represented by the above general formula (A), X + is a quaternary ammonium group, n 1 is 1, n 2 If A is 0, 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include N,N,N-trialkyl-N-vinylammonium tetrafluoroborate, N,N,N-trialkyl-N-vinylammonium trifluoroacetate, N,N,N-trialkyl-N-vinylammonium heptafluorobutyrate, N,N,N-trialkyl-N-vinylammonium trifluoromethanesulfonate, N,N,N-trialkyl-N-vinylammonium perfluorobutanesulfonate, N,N,N-trialkyl-N-vinylammonium bis(trifluoromethanesulfonyl)imide, N N,N,N-trialkyl-N-vinylammonium cation-containing ionic compounds such as N,N,N-trialkyl-N-vinylammonium bis(pentafluoroethanesulfonyl)imide, N,N,N-trialkyl-N-vinylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-vinylammonium hexafluorophosphate, N,N,N-trialkyl-N-vinylammonium(trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-vinylammonium dicyanamide, and N,N,N-trialkyl-N-vinylammonium thiocyanate;N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium tetrafluoroborate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium trifluoroacetate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium heptafluorobutyrate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium trifluoromethanesulfonate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium perfluorobutanesulfonate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium bis(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium cation-containing ionic compounds such as monoimide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium hexafluorophosphate, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium (trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium dicyanamide, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium thiocyanate, etc.N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium tetrafluoroborate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium trifluoroacetate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium heptafluorobutyrate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium trifluoromethanesulfonate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium perfluorobutanesulfonate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium bis(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium Examples of N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium cation-containing ionic compounds include mubis(pentafluoroethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium tris(trifluoromethanesulfonyl)imide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium hexafluorophosphate, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium(trifluoromethanesulfonyl)trifluoroacetamide, N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium dicyanamide, and N,N,N-trialkyl-N-(meth)acryloylaminoalkylammonium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0127] Among the ionic compounds represented by the above general formula (A), X + is a quaternary ammonium group, n 1 is 1, n 2 If A is 0, 1Preferred specific examples of the embodiment in which is a (meth)acryloyloxy group include (meth)acryloyloxypropyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxypropyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(fluorosulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(fluorosulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium trifluoromethanesulfonic acid, and (meth)acryloyloxyethyldimethylbenzylammonium trifluoromethanesulfonic acid.
[0128] Among the ionic compounds represented by the above general formula (A), X + is a quaternary ammonium group, n 1 is 1, n 2 If A is 0, 1 Preferred specific examples of the embodiment in which is a (meth)acryloylamino group include (meth)acryloylaminopropyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloylaminopropyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloylaminopropyltrimethylammonium bis(fluorosulfonyl)imide, (meth)acryloylaminopropyldimethylbenzylammonium bis(fluorosulfonyl)imide, (meth)acryloylaminopropyltrimethylammonium trifluoromethanesulfonic acid, and (meth)acryloylaminopropyldimethylbenzylammonium trifluoromethanesulfonic acid.
[0129] Among the ionic compounds represented by the above general formula (A), X + is an imidazolium group, n 1is 1, n 2 is 0 or 1, A 1 and A 2Specific examples of the embodiment in which the group is a vinyl group include 1-alkyl-3-vinylimidazolium tetrafluoroborate, 1-alkyl-3-vinylimidazolium trifluoroacetate, 1-alkyl-3-vinylimidazolium heptafluorobutyrate, 1-alkyl-3-vinylimidazolium trifluoromethanesulfonate, 1-alkyl-3-vinylimidazolium perfluorobutanesulfonate, 1-alkyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-alkyl-3-vinylimidazolium 1-alkyl-3-vinylimidazolium cation-containing ionic compounds such as bis(pentafluoroethanesulfonyl)imide, 1-alkyl-3-vinylimidazolium tris(trifluoromethanesulfonyl)imide, 1-alkyl-3-vinylimidazolium hexafluorophosphate, 1-alkyl-3-vinylimidazolium(trifluoromethanesulfonyl)trifluoroacetamide, 1-alkyl-3-vinylimidazolium dicyanamide, and 1-alkyl-3-vinylimidazolium thiocyanate; 1,2-dialkyl- 1,2-dialkyl-3-vinylimidazolium cation-containing ionic compounds such as 3-vinylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-vinylimidazolium dicyanamide, and 1,2-dialkyl-3-vinylimidazolium thiocyanate; 2-alkyl-1,3-divinylinimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-divinylinimidazolium bis(trifluoromethanesulfonyl) Examples include ionic compounds containing 2-alkyl-1,3-divinylimidazolium cations, such as 2-fonyl)imide, 2-alkyl-1,3-divinylimidazolium dicyanamide, and 2-alkyl-1,3-divinylimidazolium thiocyanate; and ionic compounds containing 1-vinylimidazolium cations, such as 1-vinylimidazolium bis(fluorosulfonyl)imide, 1-vinylimidazolium bis(trifluoromethanesulfonyl)imide, 1-vinylimidazolium dicyanamide, and 1-vinylimidazolium thiocyanate.
[0130] Among the ionic compounds represented by the above general formula (A), X + is an imidazolium group, n 1 is 1, n 2 is 0 or 1, A 1 and A 2Specific examples of the embodiment in which (meth)acryloyloxy group is included are 1-alkyl-3-(meth)acryloyloxyalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoroacetate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium heptafluorobutyrate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium trifluoromethanesulfonate, and 1-alkyl-3-(meth)ac Liloyloxyalkylimidazolium perfluorobutanesulfonate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium tris(trifluoromethanesulfonyl)imide, 1-alkyl-3-(meth)acryloyloxyalkylimida 1-alkyl-3-(meth)acryloyloxyalkylimidazolium cation-containing ionic compounds such as zolium hexafluorophosphate, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium (trifluoromethanesulfonyl) trifluoroacetamide, 1-alkyl-3-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloyloxyalkylimidazolium thiocyanate; 1,2-dialkyl-3-(meth)acrylo Ionic compounds containing 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium cations, such as yloxyalkylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1,2-dialkyl-3-(meth)acryloyloxyalkylimidazolium thiocyanate;2-alkyl-1,3-di(meth)acryloyloxyalkylimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-di(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1,3-di(meth)acryloyloxyalkylimidazolium dicyanamide, 2-alkyl-1,3-di(meth)acryloyloxyimidazolium thiocyanate, etc. Examples of midazolium cation-containing ionic compounds include 1-(meth)acryloyloxyalkylimidazolium bis(fluorosulfonyl)imide, 1-(meth)acryloyloxyalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloyloxyalkylimidazolium dicyanamide, and 1-(meth)acryloyloxyalkylimidazolium thiocyanate, among other 1-(meth)acryloyloxyalkylimidazolium cation-containing ionic compounds. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0131] Among the ionic compounds represented by the above general formula (A), X + is an imidazolium group, n 1 is 1, n 2 is 0 or 1, A 1 and A 2Specific examples of the embodiment in which (meth)acryloylamino group is included are 1-alkyl-3-(meth)acryloylaminoalkylimidazolium tetrafluoroborate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoroacetate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium heptafluorobutyrate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium trifluoromethanesulfonate, and 1-alkyl-3-(meth)ac Liloylaminoalkylimidazolium perfluorobutanesulfonate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium tris(trifluoromethanesulfonyl)imide, 1-alkyl-3-(meth)acryloylaminoalkylimida 1-alkyl-3-(meth)acryloylaminoalkylimidazolium cation-containing ionic compounds such as zolium hexafluorophosphate, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium (trifluoromethanesulfonyl) trifluoroacetamide, 1-alkyl-3-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1-alkyl-3-(meth)acryloylaminoalkylimidazolium thiocyanate; 1,2-dialkyl-3-(meth)acrylo Ionic compounds containing 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium cations, such as ylaminoalkylimidazolium bis(fluorosulfonyl)imide, 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1,2-dialkyl-3-(meth)acryloylaminoalkylimidazolium thiocyanate;2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium bis(fluorosulfonyl)imide, 2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium dicyanamide, 2-alkyl-1,3-di(meth)acryloylaminoalkylimidazolium thiocyanate, etc. Examples of ionic compounds containing midazolium cations include 1-(meth)acryloylaminoalkylimidazolium bis(fluorosulfonyl)imide, 1-(meth)acryloylaminoalkylimidazolium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloylaminoalkylimidazolium dicyanamide, and 1-(meth)acryloylaminoalkylimidazolium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0132] Among the ionic compounds represented by the above general formula (A), X + is a pyridinium group, n 1 is 1, n 2 If A is 0, 1Specific examples of embodiments in which the group is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-vinylpyridinium cation-containing ionic compounds such as 1-vinylpyridinium bis(fluorosulfonyl)imide, 1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 1-vinylpyridinium dicyanamide, and 1-vinylpyridinium thiocyanate; 1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, and 1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide. Ionic compounds containing 1-(meth)acryloyloxyalkylpyridinium cations, such as dinium bis(trifluoromethanesulfonyl)imide, 1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 1-(meth)acryloyloxyalkylpyridinium thiocyanate; 1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, and 1-(meth)acryloylaminoalkyl Ionic compounds containing 1-(meth)acryloylaminoalkylpyridinium cations, such as lupyridinium dicyanamide and 1-(meth)acryloylaminoalkylpyridinium thiocyanate; 2-alkyl-1-vinylpyridinium cations, such as 2-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-vinylpyridinium dicyanamide, and 2-alkyl-1-vinylpyridinium thiocyanate. Ionic compounds containing ionic compounds; such as 2-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, 2-alkyl-1-(meth)acryloyloxyalkylpyridinium thiocyanate, and other ionic compounds containing 2-alkyl-1-(meth)acryloyloxyalkylpyridinium cations;Ionic compounds containing 2-alkyl-1-(meth)acryloylaminoalkylpyridinium cations, such as 2-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 2-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 2-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, 2-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate; ionic compounds containing 3-alkyl-1-vinylpyridinium cations, such as 3-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 3-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-vinylpyridinium dicyanamide, 3-alkyl-1-vinyl(meth)acryloyloxyalkylpyridinium bis Ionic compounds containing 3-alkyl-1-(meth)acryloyloxyalkylpyridinium cations, such as (fluorosulfonyl)imide, 3-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 3-alkyl-1-(meth)acryloyloxyalkylpyridinium thiocyanate; ionic compounds containing 3-alkyl-1-(meth)acryloylaminoalkylpyridinium cations, such as 3-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 3-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 3-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, and 3-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate;4-alkyl-1-vinylpyridinium cation-containing ionic compounds such as 4-alkyl-1-vinylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-vinylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-vinylpyridinium dicyanamide, and 4-alkyl-1-vinylpyridinium thiocyanate; 4-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-(meth)acryloyloxyalkylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-(meth)acryloyloxyalkylpyridinium dicyanamide, and 4-alkyl-1-(meth) Examples include ionic compounds containing 4-alkyl-1-(meth)acryloyloxyalkylpyridinium cations, such as acryloyloxyalkylpyridinium thiocyanate; and ionic compounds containing 4-alkyl-1-(meth)acryloylaminoalkylpyridinium cations, such as 4-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(fluorosulfonyl)imide, 4-alkyl-1-(meth)acryloylaminoalkylpyridinium bis(trifluoromethanesulfonyl)imide, 4-alkyl-1-(meth)acryloylaminoalkylpyridinium dicyanamide, and 4-alkyl-1-(meth)acryloylaminoalkylpyridinium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0133] Among the ionic compounds represented by the above general formula (A), X + The group is a piperinidinium group, and n 1 is 1, n 2 If A is 0, 1Specific examples of embodiments in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-alkyl-1-vinylalkylpiperidinium cation-containing ionic compounds such as 1-alkyl-1-vinylalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-vinylalkylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-vinylalkylpiperidinium dicyanamide, and 1-alkyl-1-vinylalkylpiperidinium thiocyanate; 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium bis(trifluoromethanesulfonyl)imide, and 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium bis(trifluoromethanesulfonyl)imide. Examples include 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium cation-containing ionic compounds such as liloyloxyalkylpiperidinium dicyanamide and 1-alkyl-1-(meth)acryloyloxyalkylpiperidinium thiocyanate; and 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium dicyanamide and 1-alkyl-1-(meth)acryloylaminoalkylpiperidinium thiocyanate, etc. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0134] Among the ionic compounds represented by the above general formula (A), X + is a pyrrolidinium group, n 1 is 1, n 2 If A is 0, 1Specific examples of embodiments in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include 1-alkyl-1-vinylalkylpyrrolidinium cation-containing ionic compounds such as 1-alkyl-1-vinylalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-vinylalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-vinylalkylpyrrolidinium dicyanamide, and 1-alkyl-1-vinylalkylpyrrolidinium thiocyanate; 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide, and 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide. Examples include 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium cation-containing ionic compounds such as liloyloxyalkylpyrrolidinium dicyanamide and 1-alkyl-1-(meth)acryloyloxyalkylpyrrolidinium thiocyanate; and 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium bis(fluorosulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium dicyanamide and 1-alkyl-1-(meth)acryloylaminoalkylpyrrolidinium thiocyanate. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0135] Among the ionic compounds represented by the above general formula (A), X + is a trialkylsulfonium group, n 1 is 1, n 2 If A is 0, 1Specific examples of embodiments in which the group is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include dialkyl(vinyl)sulfonium cation-containing ionic compounds such as dialkyl(vinyl)sulfonium bis(fluorosulfonyl)imide, dialkyl(vinyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl(vinyl)sulfonium dicyanamide, and dialkyl(vinyl)sulfonium thiocyanate; dialkyl((meth)acryloyloxyalkyl)sulfonium bis(fluorosulfonyl)imide, dialkyl((meth)acryloyloxyalkyl)sulfonium bis(trifluoromethanesulfonyl)imide, and dialkyl((meth)acryloyloxyalkyl Examples include dialkyl((meth)acryloyloxyalkyl)sulfonium cation-containing ionic compounds such as sulfonium dicyanamide and dialkyl((meth)acryloyloxyalkyl)sulfonium thiocyanate; dialkyl((meth)acryloylaminoalkyl)sulfonium bis(fluorosulfonyl)imide, dialkyl((meth)acryloylaminoalkyl)sulfonium bis(trifluoromethanesulfonyl)imide, dialkyl((meth)acryloylaminoalkyl)sulfonium dicyanamide and dialkyl((meth)acryloylaminoalkyl)sulfonium thiocyanate, etc. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0136] Among the ionic compounds represented by the above general formula (A), X + is a quaternary phosphonium group, n 1 is 1, n 2 If A is 0, 1Specific examples of the embodiment in which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group include trialkyl(vinyl)phosphonium cation-containing ionic compounds such as trialkyl(vinyl)phosphonium bis(fluorosulfonyl)imide, trialkyl(vinyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl(vinyl)phosphonium dicyanamide, and trialkyl(vinyl)phosphonium thiocyanate; trialkyl((meth)acryloyloxyalkyl)phosphonium bis(fluorosulfonyl)imide, trialkyl((meth)acryloyloxyalkyl)phosphonium bis(trifluoromethanesulfonyl)imide, and trialkyl((meth)acryloyloxyalkyl Examples include trialkyl((meth)acryloyloxyalkyl)phosphonium cation-containing ionic compounds such as phosphonium dicyanamide and trialkyl((meth)acryloyloxyalkyl)phosphonium thiocyanate; and trialkyl((meth)acryloylaminoalkyl)phosphonium bis(fluorosulfonyl)imide, trialkyl((meth)acryloylaminoalkyl)phosphonium bis(trifluoromethanesulfonyl)imide, trialkyl((meth)acryloylaminoalkyl)phosphonium dicyanamide and trialkyl((meth)acryloylaminoalkyl)phosphonium thiocyanate, etc. The alkyl substituent is preferably an alkyl group having 1 to 16 carbon atoms, particularly preferably 1 to 12 carbon atoms, and even more preferably 1 to 6 carbon atoms.
[0137] Among the ionic compounds represented by the above general formula (A), X + is a quaternary ammonium group, n 1 is 1, n 2 A is 1, 1 and A 2Specific examples of the embodiment in which is a hydroxyl group include bis(2-hydroxyethyl)-methyl-octylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-decylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-dodecylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-tetradecylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-hexadecylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-octadecylammonium bis(trifluoromethanesulfonyl)imide, bis(2-hydroxyethyl)-methyl-(9-en-octadecyl)ammonium bis(trifluoromethanesulfonyl)imide, and ethyl-bis(2-hydroxy Examples include ethyl)-octylammonium bis(trifluoromethanesulfonyl)imide, ethyl-bis(2-hydroxyethyl)-decylammonium bis(trifluoromethanesulfonyl)imide, ethyl-bis(2-hydroxyethyl)-dodecylammonium bis(trifluoromethanesulfonyl)imide, ethyl-bis(2-hydroxyethyl)-tetradecylammonium bis(trifluoromethanesulfonyl)imide, ethyl-bis(2-hydroxyethyl)-hexadecylammonium bis(trifluoromethanesulfonyl)imide, ethyl-bis(2-hydroxyethyl)-octadecylammonium bis(trifluoromethanesulfonyl)imide, oleylbis(2-hydroxyethyl)methylammonium bis(trifluoromethanesulfonyl)imide, and oleyl-ethyl-bis(2-hydroxyethyl)ammonium bis(trifluoromethanesulfonyl)imide.
[0138] Among the ionic compounds represented by the above general formula (A), X + is a pyridinium group, n 1 is 1, n 2 If A is 0, 1Specific examples of the embodiment in which is a hydroxyl group include N-hydroxyethylpyridinium bis(trifluoromethasulfonyl)imide.
[0139] Among the ionic compounds represented by the above general formula (A), X + is an imidazolium group, n 1 is 1, n 2 If A is 0, 1 Specific examples of the embodiment in which is a hydroxyl group include 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0140] Among the ionic compounds represented by the above general formula (A), X + is an imidazolium group or a quaternary ammonium group, n 1 is 1, n 2 If A is 0, 1 and A 2 Specific examples of embodiments in which the group is an amino group include 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium dicyanamide, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, 1-aminohexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminohexyl-3-methylimidazolium dicyanamide, 1-aminohexyl-3-methylimidazolium tetrafluoroborate, trimethylaminohexylammonium bis(trifluoromethanesulfonyl)imide, trimethylaminohexylammonium dicyanamide, and trimethylaminohexylammonium tetrafluoroborate.
[0141] The reaction in which at least one of two or more polymers forms a covalent bond with a functional group (A) of an ionic compound (A) is not particularly limited in form, as long as such covalent bond formation is possible. For example, the functional group (A) may be incorporated as a monomer unit of the polymer, or it may react with a functional group on the side chain of the polymer to form a covalent bond. Furthermore, the polymer and the functional group (A) of the ionic compound (A) may react via a crosslinking agent described later to form a covalent bond.
[0142] For example, if the functional group (A) of an ionic compound (A) is a copolymerizable functional group such as a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, or a styryl group, and is included in a mixture of monomer components constituting the polymer, then it will be incorporated as a monomer unit during the polymerization process of the polymer, and a covalent bond will be formed.
[0143] Furthermore, if the functional group (A) of the ionic compound (A) is a copolymerizable functional group such as a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, or a styryl group, and is included in a partially polymerized mixture of monomer components constituting the polymer, then covalent bonds are formed by living radical polymerization with the polymerization terminal radicals of the partially polymerized compound.
[0144] Furthermore, if the functional group (A) of the ionic compound (A) is a hydroxyl group, an amino group, a mercapto group, etc., and the polymer has a functional group in its side chain that can react with the functional group (A), such as an isocyanate group, a thioisocyanate group, or an epoxy group, or if the functional group (A) is an epoxy group, etc., and the polymer has a functional group in its side chain that can react with the functional group (A), such as a hydroxyl group, an amino group, or a mercapto group, then the polymer reacts with the functional group (A) to form a covalent bond.
[0145] Furthermore, if the functional group (A) of the ionic compound (A) is a hydroxyl group, an amino group, a mercapto group, etc., and the polymer has a hydroxyl group, an amino group, a mercapto group, etc. in its side chain, then by incorporating the crosslinking agent described later, the functional group (A) and the side chain functional group of the polymer may react with the isocyanate group, thioisocyanate group, epoxy group, etc. of the crosslinking agent to form a covalent bond via the crosslinking agent.
[0146] The content of the ionic compound of the present invention is not particularly limited, but in order to impart sufficient antistatic performance to the adhesive layer of the present invention, it may preferably contain 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, even more preferably 0.1 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, 2.0 parts by weight or more, 3.0 parts by weight or more, 4.0 parts by weight or more, or 5.0 parts by weight or more, per 100 parts by weight (total amount) of two or more polymers. The content of the ionic compound of the present invention is not particularly limited, but in order to make it easier to ensure durability such as transparency, appearance and adhesive reliability in the adhesive layer of the present invention, it may preferably contain 50 parts by weight or less, more preferably 40 parts by weight or less, even more preferably 30 parts by weight or less, 25 parts by weight or less, 20 parts by weight or less, or 15 parts by weight or less, per 100 parts by weight (total amount) of two or more polymers.
[0147] [1-10. Conductive Polymers (B)] In the adhesive composition of the present invention, it is preferable that at least one of the two or more polymers is a conductive polymer (B) that forms a covalent bond with the ionic compound of the present invention. The configuration in which the adhesive composition of the present invention includes a conductive polymer (B) that forms a covalent bond with the ionic compound of the present invention is preferable because it is less likely to cause defects such as corrosion of metal wiring due to the deposition of the ionic compound on the surface of the adhesive layer, and it is possible to suppress the increase in surface resistance in a humid and hot environment and maintain excellent antistatic properties. Furthermore, it is also preferable because it reduces the compatibility between the adhesive layer and the ionic compound, which can prevent defects in transparency and appearance such as clouding, as well as foaming and peeling, especially in a humid and hot environment.
[0148] The conductive polymer (B) is at least one of two or more polymers included in the adhesive composition of the present invention, and is a polymer that forms a covalent bond with the ionic compound of the present invention. The polymer constituting the conductive polymer (B) can be the same polymer as the adhesive polymer (A). Among these, acrylic polymers are preferred for the conductive polymer (B) due to their transparency, weather resistance, adhesive reliability, and the abundance of monomer types, which facilitates the design of solvent-type compositions and solvent-free (active energy ray curing) compositions. In other words, the adhesive composition of the present invention is preferably an acrylic adhesive composition containing an acrylic polymer as the adhesive polymer (A), and further containing an acrylic polymer as the conductive polymer (B). The conductive polymer (B) can be used alone or in combination of two or more types.
[0149] The acrylic polymer constituting the conductive polymer (B) can be the same as the acrylic polymer (A) described above. In particular, the acrylic polymer constituting the conductive polymer (B) is preferably a polymer containing the above-mentioned (meth)acrylate alkoxyalkyl ester as an essential monomer unit, from the viewpoint of making it easier to impart conductivity.
[0150] The content (percentage) of the above-mentioned (meth)acrylate alkoxyalkyl ester in the total monomer units of the acrylic polymer constituting the conductive polymer (B) is not particularly limited, but from the viewpoint of efficiently forming a sea-island structure, it is preferably 50 to 99 parts by weight, more preferably 70 to 98 parts by weight, and even more preferably 80 to 95 parts by weight, based on the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer constituting the conductive polymer (B).
[0151] The content (percentage) of the ionic compound of the present invention in the conductive polymer (B) is not particularly limited, but from the viewpoint of achieving excellent antistatic properties, it is preferably 0.1 to 20 parts by weight, more preferably 1 to 15 parts by weight, and even more preferably 2 to 10 parts by weight per 100 parts by weight of conductive polymer (B).
[0152] The conductive polymer (B) can be produced by using the above-mentioned ionic compound (A) as the ionic compound of the present invention, reacting the functional group (A) of the ionic compound (A) with at least one polymer from two or more polymers to form a covalent bond. From the viewpoint of efficiently forming the sea-island structure described later, it is preferable that the functional group (A) of the ionic compound (A) is a copolymerizable functional group such as a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, or a styryl group, and is included in a mixture of monomer components of the acrylic polymer constituting the conductive polymer (B) or a partial polymer thereof, and is incorporated as a monomer unit in the polymerization process of the acrylic polymer, thereby forming a covalent bond.
[0153] The content of conductive polymer (B) in the adhesive composition of the present invention is not particularly limited, but is preferably 10 to 99% by weight, more preferably 30 to 97% by weight, and even more preferably 50 to 95% by weight. A configuration in which the conductive polymer (B) content is 10% by weight or more is preferable because it allows the adhesive composition of the present invention to form a sea-island structure with phase separation into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) contains the ionic compound of the present invention, thereby achieving excellent antistatic properties. Furthermore, a configuration in which the conductive polymer (B) content is 99% by weight or less is preferable because it can impart excellent tackiness to the adhesive layer of the present invention.
[0154] In the adhesive composition of the present invention, the weight ratio of the conductive polymer (B) to the adhesive polymer (A) (conductive polymer (B) / adhesive polymer (A)) is preferably 10 / 90 to 99 / 1. The configuration in which the weight ratio is 10 / 90 or more is preferred in that the adhesive composition of the present invention forms a sea-island structure in which a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention, thereby achieving excellent antistatic properties. More preferably, the weight ratio is 12 / 88 or more, even more preferably 15 / 85 or more, and particularly preferably 20 / 80 or more. Furthermore, the configuration in which the weight ratio is 99 / 1 or less is preferred in that it can impart excellent tackiness to the adhesive layer of the present invention. More preferably, the weight ratio is 97 / 3 or less, even more preferably 95 / 5 or less, and particularly preferably 93 / 7 or less.
[0155] [1-11. Antistatic agents other than ionic compounds of the present invention] The adhesive composition of the present invention may optionally contain antistatic agents other than the ionic compounds of the present invention (which may be referred to as "other antistatic agents" in this specification). Other antistatic agents include, for example, ionic surfactants, conductive polymers, conductive fine particles, and other materials that can impart antistatic properties.
[0156] Examples of ionic surfactants include cationic surfactants (e.g., quaternary ammonium salt type, phosphonium salt type, sulfonium salt type, etc.), anionic surfactants (carboxylic acid type, sulfonate type, sulfate type, phosphate type, phosphite type, etc.), amphoteric surfactants (sulfobetaine type, alkylbetaine type, alkylimidazolium betaine type, etc.), or nonionic surfactants (polyhydric alcohol derivatives, β-cyclodextrin inclusion compounds, sorbitan fatty acid monoesters / diesters, polyalkylene oxide derivatives, amine oxides, etc.).
[0157] Examples of conductive polymers include polyaniline-based, polythiophene-based, polypyrrole-based, and polyquinoxaline-based polymers, but among these, polyaniline and polythiophene are preferred. Polythiophene is particularly preferred.
[0158] Examples of conductive fine particles include metal oxides such as tin oxide, antimony oxide, indium oxide, and zinc oxide. Among these, tin oxide is preferred. Examples of tin oxide include tin oxide, antimony-doped tin oxide, indium-doped tin oxide, aluminum-doped tin oxide, tungsten-doped tin oxide, titanium oxide-cerium oxide-tin oxide composites, and titanium oxide-tin oxide composites. The average particle size of the fine particles is about 1 to 100 nm, preferably 2 to 50 nm.
[0159] Furthermore, examples of antistatic agents other than those mentioned above include acetylene black, Ketjen black, natural graphite, artificial graphite, titanium black, and ionic conductive polymers such as homopolymers of monomers having cationic (quaternary ammonium salts, etc.), amphoteric (betaine compounds, etc.), anionic (sulfonates, etc.), or nonionic (glycerin, etc.) ionic conductive groups, copolymers of such monomers with other monomers, polymers having acrylate or methacrylate-derived parts with quaternary ammonium bases, and hydrophilic polymers such as polyethylene methacrylate copolymers alloyed with acrylic resins, etc.
[0160] If the adhesive composition of the present invention contains other antistatic agents, the content thereof is not particularly limited, but from the viewpoint of ensuring the transparency, appearance, adhesion reliability, and other durability of the adhesive layer of the present invention, it is preferably 1 part by weight or less per 100 parts by weight (total amount) of two or more polymers, and more preferably 0.5 parts by weight or less, 0.4 parts by weight or less, 0.3 parts by weight or less, or 0.2 parts by weight or less. If the adhesive composition of the present invention contains other antistatic agents, the lower limit of the content is not particularly limited, but it may be 0.01 parts by weight or more, or 0.05 parts by weight or more per 100 parts by weight (total amount) of two or more polymers.
[0161] [1-12. Additives] The adhesive composition of the present invention may optionally contain known additives such as crosslinking agents, crosslinking accelerators, silane coupling agents, tackifying resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), anti-aging agents, fillers, colorants (pigments, dyes, etc.), ultraviolet absorbers, antioxidants, chain transfer agents, plasticizers, softeners, surfactants, and rust inhibitors, to the extent that they do not impair the properties of the present invention. Such additives may be used individually or in combination of two or more.
[0162] The presence of a crosslinking agent in the adhesive composition of the present invention facilitates the crosslinking of the base polymer to increase the gel fraction and improve foaming resistance and peeling. It also facilitates the efficient formation of the sea-island structure described later. For example, by crosslinking an acrylic polymer (particularly acrylic polymer (A)), the gel fraction can be easily controlled and increased, thus improving foaming resistance and peeling. Furthermore, at least one of two or more polymers can form a covalent bond with the ionic compound (A) via the crosslinking agent.
[0163] Examples of the crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. In particular, when the adhesive composition of the present invention is an adhesive layer containing an acrylic polymer as the base polymer, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred, and isocyanate-based crosslinking agents are more preferred, in terms of improving foaming resistance and peeling properties. The crosslinking agents may be used alone or in combination of two or more types.
[0164] Examples of the above-mentioned isocyanate-based crosslinking agents (polyfunctional isocyanate compounds) include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. In addition, commercially available isocyanate-based crosslinking agents include, for example, trimethylolpropane / tolylene diisocyanate adduct [manufactured by Nippon Polyurethane Industries Co., Ltd., product name "Coronate L"], trimethylolpropane / hexamethylene diisocyanate adduct [manufactured by Nippon Polyurethane Industries Co., Ltd., product name "Coronate HL"], and trimethylolpropane / xylylene diisocyanate adduct [manufactured by Mitsui Chemicals, Inc., product name "Takenate D-110N"].
[0165] Examples of the epoxy crosslinking agents (polyfunctional epoxy compounds) mentioned above include N,N,N',N'-tetraglycidyl-m-xylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polypropylene Examples of epoxy crosslinking agents include lysidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate ester, diglycidyl o-phthalate ester, triglycidyl-tris(2-hydroxyethyl) isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. In addition, commercially available epoxy crosslinking agents such as "Tetrad C" manufactured by Mitsubishi Gas Chemical Co., Ltd. can also be used.
[0166] The crosslinking agent content in the adhesive composition of the present invention is not particularly limited, but for example, it is preferably 0.001 to 10 parts by weight, and more preferably 0.01 to 5 parts by weight, per 100 parts by weight (total amount) of two or more polymers. A crosslinking agent content of 0.001 parts by weight or more is preferable because it tends to improve foaming resistance and peeling. On the other hand, a crosslinking agent content of 10 parts by weight or less is preferable because it allows the adhesive layer to have appropriate flexibility and tends to improve adhesive strength.
[0167] The presence of a silane coupling agent in the adhesive composition of the present invention is preferable because it facilitates obtaining excellent adhesion to glass (particularly excellent adhesive reliability to glass at high temperature and high humidity). The silane coupling agent is not particularly limited, but examples include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-phenyl-aminopropyltrimethoxysilane. Among these, γ-glycidoxypropyltrimethoxysilane is preferred. Furthermore, commercially available products such as the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can also be used as the silane coupling agent. The silane coupling agent may be used alone or in combination of two or more types.
[0168] The content of the silane coupling agent in the adhesive composition of the present invention is not particularly limited, but for example, if the adhesive composition of the present invention is an adhesive layer containing an acrylic polymer as the base polymer, then from the viewpoint of improving adhesion reliability to glass, it is preferably 0.01 to 1 part by weight, and more preferably 0.03 to 0.5 parts by weight, per 100 parts by weight (total amount) of two or more polymers.
[0169] The adhesive composition of the present invention is preferable if it contains a coloring agent (such as a pigment or dye) because it can prevent reflections caused by metal wiring or metal oxides such as ITO, and can also contribute to preventing RGB color mixing and improving contrast.
[0170] The coloring agent may be a dye or a pigment, as long as it is soluble or dispersible in the adhesive composition of the present invention. Dyes are preferred because they can achieve low haze even with small amounts of addition, and they do not settle like pigments, making them easy to distribute uniformly. Pigments are also preferred because they exhibit high color development even with small amounts of addition. When using a pigment as the coloring agent, it is preferable that it has low or no conductivity. When using a dye, it is preferable to use it in combination with an antioxidant or the like.
[0171] Examples of pigments include Tokushiki's "9050BLACK," "UVBK-0001," carbon black, and titanium black. Examples of dyes include Orient Chemical Industry's "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802."
[0172] The colorant content in the adhesive composition of the present invention is, for example, about 0.01 to 20 parts by weight per 100 parts by weight (total amount) of two or more polymers, and can be appropriately set depending on the type of colorant, the color tone of the adhesive layer, and the light transmittance. The colorant may also be added to the composition as a solution or dispersion obtained by dissolving or dispersing it in a suitable solvent.
[0173] [1-13.Sea-island structure] The adhesive composition of the present invention has a sea-island structure in which a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention. The configuration in which the continuous phase (sea portion) of the sea-island structure of the adhesive composition of the present invention contains the ionic compound of the present invention is preferable because the ionic compound of the present invention efficiently forms paths for imparting conductivity in the continuous phase, and the adhesive layer of the present invention exhibits a low surface resistivity and has excellent antistatic performance.
[0174] The term "sea-island structure" above refers to a structure in which a discontinuous phase (island portion) consisting of at least one polymer from two or more polymers is dispersed in a continuous phase (sea portion) consisting of another polymer. The sea-island structure can be confirmed by observing thin sections prepared from a frozen sample using a transmission electron microscope (TEM). In this specification, a form in which the adhesive composition of the present invention has a sea-island structure separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) contains the ionic compound of the present invention, may be referred to as the "sea-island structure of the present invention."
[0175] In the adhesive composition of the present invention, the discontinuous phase (island portion) preferably contains the adhesive polymer (A). The configuration in which the discontinuous phase (island portion) contains the adhesive polymer (A) is preferable because it can impart excellent tackiness to the adhesive layer of the present invention without impairing excellent antistatic performance.
[0176] The configuration in which the discontinuous phase (island portion) contains the adhesive polymer (A) can be achieved by the content of the adhesive polymer (A) in the adhesive composition of the present invention, the ratio of the adhesive polymer (A) to the conductive polymer (B), and the method for forming the sea-island structure described later.
[0177] In the sea-island structure of the present invention, the discontinuous phase (island portion) may contain the ionic compound of the present invention. The configuration in which the discontinuous phase (island portion) contains the ionic compound of the present invention is preferable because the adhesive layer of the present invention exhibits an even lower surface resistivity and has excellent antistatic performance.
[0178] The configuration in which the discontinuous phase (island portion) contains the ionic compound of the present invention is not particularly limited, but can be realized, for example, by using the ionic compound (A) as the ionic compound of the present invention, and reacting the functional group (A) of the ionic compound (A) with the polymer constituting the discontinuous phase (island portion) to form a covalent bond.
[0179] Methods for forming the sea-island structure of the present invention include forming a block copolymer of the adhesive polymer (A) and the conductive polymer (B), and forming a phase-separated structure by adding an adhesive monomer and a photopolymerization initiator to the conductive polymer and curing it with UV light. Of these, the method of forming a block copolymer of the adhesive polymer (A) and the conductive polymer (B) is preferred because it can realize a microphase-separated sea-island structure with an average diameter of discontinuous phases (islands) on the order of nanometers. In this specification, the block copolymer formed from the adhesive polymer (A) and the conductive polymer (B) may be referred to as the "block copolymer of the present invention."
[0180] [1-14. Block Copolymer of the Present Invention] The block copolymers of the present invention are described below, but the present invention is not limited thereto. The block copolymer of the present invention is formed from an adhesive polymer (A) and a conductive polymer (B), that is, it has segments made of adhesive polymer (A) and segments made of conductive polymer (B). In this specification, the segments made of adhesive polymer (A) may be referred to as "adhesive segments (A)," and the segments made of conductive polymer (B) may be referred to as "conductive segments (B)." In adhesive segments (A) and conductive segments (B), "segment" refers to a substructure that constitutes each block unit of the block copolymer of the present invention.
[0181] The aforementioned sea-island structure is thought to be formed in the block copolymer contained in the adhesive composition of the present invention by the aggregation of adhesive segments (A) and conductive segments (B) through pseudo-crosslinking, with each forming a phase and then separating. Whether the phase derived from the adhesive segments (A) or the phase derived from the conductive segments (B) forms a continuous phase (sea portion) or a discontinuous phase (island portion) is not particularly limited, but can be adjusted by the type of block copolymer, monomer composition and amount, the type of each segment (adhesive segment (A) and conductive segment (B)), monomer composition and amount, and the type and amount of crosslinking agent.
[0182] The structure of the block copolymer of the present invention may be a linear block copolymer, a branched (star-shaped) block copolymer, or a mixture thereof. The structure of such a block copolymer may be appropriately selected depending on the desired physical properties of the block copolymer, but from the viewpoint of cost and ease of manufacture, a linear block copolymer is preferred. Furthermore, the linear block copolymer may have any structure (arrangement), (AB) n Type, (AB) n- Preferably, the block copolymer has at least one structure selected from the group consisting of type A (where n is an integer of 1 or more, for example, an integer from 1 to 3). In these structures, A and B refer to segments composed of different monomer compositions. In this specification, the segment represented by A that constitutes the linear block copolymer may be referred to as the "A segment," and the segment represented by B may be referred to as the "B segment."
[0183] Among these, from the viewpoint of ease of manufacture, AB-type diblock copolymers and ABA-type triblock copolymers represented by ABA are preferred, and ABA-type triblock copolymers are more preferred. It is believed that ABA-type triblock copolymers can exhibit a sea-island structure in which the A segments and B segments are microphase-separated on an nm scale by pseudo-crosslinking between the A segments at both ends. In ABA-type triblock copolymers, the two A segments located at both ends may be identical or different.
[0184] If the block copolymer of the present invention is an ABA-type triblock copolymer, then it is sufficient that at least one of the two A segments and one B segment (a total of three) is an adhesive segment (A) and at least one other is a conductive segment (B). From the viewpoint of ease of manufacture, etc., an ABA-type triblock copolymer in which the A segments are the adhesive segment (A) and the B segments are the conductive segment (B) is preferred. In that case, an ABA-type triblock copolymer in which at least one of the two A segments is an adhesive segment (A) and the B segment is a conductive segment (B) is preferred, and an ABA-type triblock copolymer in which both of the two A segments are adhesive segments (A) and the B segments are conductive segments (B) is more preferred.
[0185] The block copolymer of the present invention is composed of a plurality of segments (including an adhesive segment (A) and a conductive segment (B)) obtained by polymerizing monomer components.
[0186] The monomer units constituting the adhesive segment (A) can be the same as the monomer units of the acrylic polymer (A) constituting the adhesive polymer (A).
[0187] The monomer units constituting the conductive segment (B) can be the same as those used for the monomer units of the acrylic polymer constituting the conductive polymer (B), and furthermore, the ionic compound (A) of the present invention can be used as the ionic compound of the present invention. Since the production of the block copolymer of the present invention is easy, it is preferable that the functional group (A) of the ionic compound (A) is a copolymerizable functional group such as a (meth)acryloyloxy group, a (meth)acryloylamino group, a vinyl group, an allyl group, or a styryl group, and that it is incorporated as a monomer unit during the polymerization of the conductive segment (B) and that a covalent bond is formed.
[0188] The ionic compound (A) used in the production of the block copolymer of the present invention is, in the above formula (A), X + is a quaternary ammonium group, n 1 is 1, n 2 If A is 0, 1An ionic compound which is a vinyl group, a (meth)acryloyloxy group, or a (meth)acryloylamino group is preferred, N,N,N-trialkyl-N-(meth)acryloyloxyalkylammonium bis(trifluoromethanesulfonyl)imide is more preferred, and (meth)acryloyloxypropyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxypropyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(trifluoromethanesulfonyl)imide, (meth)acryloyloxyethyltrimethylammonium bis(fluorosulfonyl)imide, (meth)acryloyloxyethyldimethylbenzylammonium bis(fluorosulfonyl)imide, etc. are even more preferred.
[0189] The block copolymer of the present invention can be produced by the living radical polymerization method of the above monomer components. The living radical polymerization method maintains the simplicity and versatility of the conventional radical polymerization method, while side reactions such as termination reactions and chain transfer are less likely to occur, and the growing end grows without deactivation, so it is preferred in terms of precise control of the molecular weight distribution and easy production of polymers with a uniform composition.
[0190] In the living radical polymerization method, the adhesive segment (A) may be produced first, and the monomer of the conductive segment (B) may be polymerized with the adhesive segment (A); the conductive segment (B) may be produced first, and the monomer of the adhesive segment (A) may be polymerized with the conductive segment (B).
[0191] When the block copolymer of the present invention is an ABA type triblock copolymer, from the viewpoint of ease of production, it is preferable to produce the A segment first and polymerize the monomer of the B segment with the A segment.
[0192] The living radical polymerization method described above can use known methods without particular limitation, and depending on the method of stabilizing the polymerization growth ends, there are methods such as the method using a transition metal catalyst (ATRP method); the method using a sulfur-based reversible addition-cleavage chain transfer agent (RAFT agent) (RAFT method); and the method using an organotellurium compound (TERP method). Among these methods, the RAFT method is preferred from the viewpoint of the diversity of monomers that can be used, the ease of molecular weight control, and the fact that no metal remains in the adhesive composition.
[0193] The RAFT method described above can use known methods without particular limitation, for example, a step 1 (first RAFT polymerization) in which monomer components are polymerized using a RAFT agent to prepare a first segment, and a step 2 (second RAFT polymerization) in which monomer components different from the monomer composition in step 1 are further added and polymerized to the first segment obtained in step 1 to add a second segment to the first segment. After the second RAFT polymerization, third, fourth, etc. RAFT polymerization may be carried out in the same manner as the second RAFT polymerization to further add the third, fourth, etc. segments.
[0194] Steps 1 and 2 can be carried out by known and conventional methods, such as solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by heat or active energy ray irradiation (thermal polymerization, active energy ray polymerization). Among these, solution polymerization is preferred in terms of transparency, water resistance, and cost. Polymerization is preferably carried out while avoiding contact with oxygen in order to suppress polymerization inhibition by oxygen. For example, polymerization is preferably carried out under a nitrogen atmosphere.
[0195] When the block copolymer of the present invention is an ABA-type triblock copolymer, it is preferable to prepare the A segment in step 1 and then add the B segment to the obtained A segment in step 2. In this case, it is preferable that the A segment is an adhesive segment (A) and the B segment is a conductive segment (B).
[0196] Any known RAFT agent can be used without particular limitation, and for example, compounds represented by the following formulas (a), (b), or (c) (trithiocarbonate, dithioester, dithiocarbonate) are preferred. [ka] [ka] [ka]
[0197] In equation (a), equation (b), or equation (c) [equations (a) to (c)], R 1a and R 1b R represents a hydrogen atom, a hydrocarbon group, or a cyano group, either identically or differently. 1c R represents a hydrocarbon group which may have a cyano group. 1a , R 1b , and R 1c Examples of hydrocarbon groups include hydrocarbon groups having 1 to 20 carbon atoms (linear, branched, or cyclic saturated or unsaturated hydrocarbon groups, etc.), with hydrocarbon groups having 1 to 12 carbon atoms being preferred. Specifically, examples of the above hydrocarbon groups include linear, branched, or cyclic alkyl groups having 1 to 18 carbon atoms (preferably 1 to 12 carbon atoms), such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, and octadecyl groups; aryl groups having 6 to 12 carbon atoms, such as phenyl groups; and arylalkyl groups with a total of 7 to 10 carbon atoms, such as benzyl and phenethyl groups. 1c Examples of hydrocarbon groups having a cyano group include groups in which 1 to 3 of the hydrogen atoms of the aforementioned hydrocarbon group are replaced by cyano groups.
[0198] In formulas (a) to (c), R 2This refers to a hydrocarbon group, or a group in which some of the hydrogen atoms of the hydrocarbon group are substituted with a carboxyl group (for example, a carboxyalkyl group). Examples of the hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (linear, branched, or cyclic saturated or unsaturated hydrocarbon groups, etc.), with hydrocarbon groups having 1 to 12 carbon atoms being preferred. Specifically, examples of hydrocarbon groups include linear, branched, or cyclic alkyl groups having 1 to 18 carbon atoms (preferably 1 to 12 carbon atoms), such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, and octadecyl groups; and arylalkyl groups having a total of 7 to 10 carbon atoms, such as benzyl and phenethyl groups.
[0199] In the RAFT method, polymerization proceeds by reacting in such a way that the starting monomer is inserted between the sulfur atom in the RAFT agent shown in formulas (a) to (c) and the methylene group adjacent to that sulfur atom.
[0200] Many of the aforementioned RAFT agents are commercially available. Those that are not commercially available can be easily synthesized by known or conventional methods. In this invention, one RAFT agent may be used alone, or two or more may be used in combination.
[0201] Examples of RAFT agents include trithiocarbonates such as dibenzyl trithiocarbonate and S-cyanomethyl-S-dodecyl trithiocarbonate; dithioesters such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate, and acetoxyethyl dithiobenzoate; and dithiocarbonates such as O-ethyl-S-(1-phenylethyl)dithiocarbonate, O-ethyl-S-(2-propoxyethyl)dithiocarbonate, and O-ethyl-S-(1-cyano-1-methylethyl)dithiocarbonate. Of these, trithiocarbonates are preferred, and trithiocarbonates having a symmetrical structure in formula (1) are more preferred, with dibenzyl trithiocarbonate and bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl}trithiocarbonate being particularly preferred.
[0202] Step 1 can be carried out by polymerizing the monomer components in the presence of a RAFT agent. In Step 1, the amount of RAFT agent used is usually 0.05 to 20 parts by weight, preferably 0.05 to 10 parts by weight, per 100 parts by weight of the total amount of monomer components. With such an amount, the reaction can be easily controlled, and the weight-average molecular weight of the resulting segments can be easily controlled. Step 2 can be carried out by adding monomer components to the polymerization reaction mixture obtained in Step 1 and further polymerization.
[0203] The RAFT method is preferably carried out in the presence of a polymerization initiator. Examples of polymerization initiators include conventional organic polymerization initiators, specifically peroxides and azo compounds, with azo compounds being preferred among these. One polymerization initiator or two or more can be used.
[0204] Examples of peroxide-based polymerization initiators include benzoyl peroxide and tert-butyl permaleate. Examples of azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitride), 2-(carbamoylazo)isobutyronitrile, and 2-phenylazo-4-methoxy-2,4- Examples include dimethylvaleronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis(N,N'-dimethylene isobutylamidine), 2,2'-azobis(isobutylamide)dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].
[0205] The amount of polymerization initiator used is typically 0.001 to 2 parts by weight, preferably 0.002 to 1 part by weight, per 100 parts by weight of the total amount of monomer components. With such an amount, it is easy to control the weight-average molecular weight of the resulting segments.
[0206] The RAFT method may be bulk polymerization without using a polymerization solvent, but it is preferable to use a polymerization solvent. Examples of the polymerization solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. The polymerization solvent can be used alone or in combination of two or more.
[0207] The amount of the polymerization solvent used is not particularly limited. For example, it is preferably 0.01 mL or more, more preferably 0.05 mL or more, and still more preferably 0.1 mL or more per 1 g of the monomer component, and preferably 50 mL or less, more preferably 10 mL or less, and still more preferably 1 mL or less.
[0208] The reaction temperature in the RAFT method is usually 60 to 120 °C, preferably 70 to 110 °C, and is usually carried out in an inert gas atmosphere such as nitrogen gas. This reaction can be carried out under any of normal pressure, increased pressure, and reduced pressure conditions, and is usually carried out under normal pressure. The reaction time is usually 1 to 20 hours, preferably 2 to 14 hours.
[0209] The polymerization reaction conditions of the above RAFT method can be applied to each of Step 1 and Step 2.
[0210] After the polymerization reaction is complete, the resulting reaction mixture can be separated from the target block copolymer of the present invention by removing the solvent and residual monomers using conventional separation and purification methods.
[0211] When preparing the adhesive segment (A) or conductive segment (B) of the block copolymer of the present invention in step 1, the weight-average molecular weight (Mw) of the adhesive segment (A) or low-conductivity segment (B) is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000. Having the Mw of the adhesive segment (A) or conductive segment (B) within this range is favorable for achieving the effects of the present invention described above. The aforementioned Mw is the sum of the Mw of adhesive segments (A) or conductive segments (B) if the block copolymer of the present invention contains two or more such segments.
[0212] The weight-average molecular weight (Mw) of the block copolymer of the present invention is not particularly limited, but is preferably 200,000 or more, more preferably 300,000 to 5,000,000, and even more preferably 400,000 to 2,500,000. Having the Mw of the block copolymer of the present invention within this range is favorable for achieving the effects of the present invention described above.
[0213] The molecular weight distribution (Mw / Mn) of the block copolymer of the present invention is not particularly limited, but is preferably greater than 1, more preferably 1.5 or more, even more preferably 2 or more, particularly preferably 2.5 or more, preferably 5 or less, more preferably 4.5 or less, even more preferably 4 or less, and particularly preferably 3.5 or less.
[0214] The weight-average molecular weight (Mw) and molecular weight distribution (Mw / Mn) mentioned above are measured by the GPC method.
[0215] The content of the adhesive segment (A) in the block copolymer of the present invention is not particularly limited, but is preferably 1 to 50% by weight, more preferably 3 to 45% by weight, and even more preferably 5 to 40% by weight. A configuration in which the content of the adhesive segment (A) is 1% by weight or more is preferable in that it can impart excellent tackiness to the adhesive layer of the present invention. Furthermore, a configuration in which the content of the adhesive segment (A) is 50% by weight or less is preferable in that the adhesive composition of the present invention can form a sea-island structure in which the phases are separated into a continuous phase and a discontinuous phase, and the continuous phase (sea portion) contains the ionic compound of the present invention.
[0216] The content of conductive segment (B) in the block copolymer of the present invention is not particularly limited, but is preferably 50 to 99% by weight, more preferably 55 to 97% by weight, and even more preferably 60 to 95% by weight. A configuration in which the content of conductive segment (B) is 1% by weight or more is preferable in that the adhesive composition of the present invention can form a sea-island structure in which a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention, thereby achieving excellent antistatic properties. Furthermore, a configuration in which the content of conductive segment (B) is 99% by weight or less is preferable in that it can impart excellent tackiness to the adhesive layer of the present invention.
[0217] In the block copolymer of the present invention, the weight ratio of the conductive segment (B) to the adhesive segment (A) (conductive segment (B) / adhesive segment (A)) is preferably 50 / 50 to 99 / 1. The configuration in which the weight ratio is 50 / 50 or more is preferred in that the adhesive composition of the present invention forms a sea-island structure in which the phases of a continuous phase and a discontinuous phase are separated, and the continuous phase (sea portion) contains the ionic compound of the present invention, thereby achieving excellent antistatic properties. More preferably, it is 55 / 45 or more, even more preferably 60 / 40 or more, and particularly preferably 65 / 35 or more. Furthermore, the configuration in which the weight ratio is 99 / 1 or less is preferred in that it can impart excellent tackiness to the adhesive layer of the present invention. More preferably, it is 97 / 3 or less, even more preferably 95 / 5 or less, and particularly preferably 93 / 7 or less.
[0218] The content of each segment and their ratios can be calculated from the amount of monomer components used in each step of the RAFT method, and can be controlled by the monomer charging ratio and polymerization rate of each monomer when forming each segment.
[0219] The content of the block copolymer of the present invention in the adhesive composition of the present invention is not particularly limited, but is preferably 75% by weight or more (e.g., 75 to 100% by weight), and more preferably 85% by weight or more (e.g., 85 to 99.99% by weight).
[0220] [2. Adhesive layer] The adhesive layer of the present invention is an adhesive layer formed by the adhesive composition of the present invention. The adhesive layer of the present invention has excellent antistatic properties. Therefore, when bonding an image display device and an optical component via the adhesive layer of the present invention, display defects due to static electricity can be suppressed. Thus, the adhesive layer of the present invention is suitably used in the manufacture of image display devices.
[0221] The surface resistivity (according to JIS K 6271) of the adhesive layer of the present invention (the adhesive layer formed by the adhesive composition of the present invention) is preferably 1.0 × 10⁻⁶ from the viewpoint of excellent antistatic performance.11 It is less than or equal to Ω / □, and more preferably 0.5 × 10 11 It is less than or equal to Ω / □, and more preferably 1.0 × 10 10 It is less than or equal to Ω / □, and 0.5 × 10 10 It is less than or equal to Ω / □. The lower limit of the surface resistivity of the adhesive layer of the present invention is not particularly limited, but is 1.0 × 10 5 Ω / □ or greater, or 0.5 × 10 5 It may be Ω / □ or greater.
[0222] The surface resistivity of the adhesive layer of the present invention can be measured by the method described in the examples below. The surface resistivity of the adhesive layer of the present invention can be adjusted by the type of adhesive polymer (A), the type and amount of adhesive segments (A), the monomer composition and amount, the type and amount of the ionic compound of the present invention, the type of conductive polymer (B), the type and amount of conductive segments (B), the monomer composition and amount, the type and amount of crosslinking agent, the ratio of adhesive polymer (A) to conductive polymer (B), the ratio of adhesive segments (A) to conductive segments (B), and the method for forming the sea-island structure described above.
[0223] The adhesive layer of the present invention (the adhesive layer formed by the adhesive composition of the present invention) is transparent or has transparency. Therefore, it offers excellent visibility and appearance through the adhesive layer of the present invention. Thus, the adhesive layer of the present invention is suitably used for optical applications.
[0224] The haze of the adhesive layer of the present invention (the adhesive layer formed by the adhesive composition of the present invention) is not particularly limited (according to JIS K7136), but is preferably 3% or less, more preferably 1% or less, 0.7% or less, or 0.6% or less. A haze of 3% or less is preferable because it provides excellent transparency and a good appearance. The haze can be measured, for example, by preparing an adhesive layer (thickness: 100 μm), leaving it standing at room temperature (23°C, 50% RH) for at least 24 hours, and then attaching it to a glass slide (for example, one with a total light transmittance of 92% and a haze of 0.2%) as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., product name "HM-150N").
[0225] The total light transmittance of the adhesive layer of the present invention in the visible light wavelength range (according to JIS K7361-1) is not particularly limited, but is preferably 90% or more, more preferably 91% or more, or 92% or more. A total light transmittance of 90% or more is preferable because it provides excellent transparency and a good appearance. The total light transmittance can be measured, for example, by preparing an adhesive layer (thickness: 100 μm), leaving it at normal conditions (23°C, 50% RH) for at least 24 hours, peeling off the release liner if one is present, and attaching it to a glass slide (for example, one with a total light transmittance of 92% and haze of 0.2%) as a sample, and measuring it using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., product name "HM-150N").
[0226] The total light transmittance and haze of the adhesive layer of the present invention can be measured by the method described in the examples below. The total light transmittance and haze of the adhesive layer of the present invention can be adjusted by adjusting the type of adhesive polymer (A), the type and amount of adhesive segments (A), the monomer composition and amount, the type and amount of the ionic compound of the present invention, the type of conductive polymer (B), the type and amount of conductive segments (B), the monomer composition and amount, the type and amount of crosslinking agent, the ratio of adhesive polymer (A) to conductive polymer (B), the ratio of adhesive segments (A) to conductive segments (B), and the method of forming the sea-island structure described above.
[0227] The gel fraction (proportion of solvent-insoluble components) of the adhesive layer of the present invention is not particularly limited, but is preferably 40-95%, more preferably 50-92%, and even more preferably 55-90%. When the gel fraction is 40% or more, the cohesive force of the adhesive layer is improved, which suppresses foaming and peeling at the interface with the adherend in high-temperature environments, dents during handling, and contamination of edges during processing, making it easier to obtain excellent foaming and peeling resistance, which is preferable. When the gel fraction is 95% or less, a moderate flexibility is obtained, which further improves adhesion and step-following ability, which is preferable.
[0228] The gel fraction (proportion of solvent-insoluble components) mentioned above is specifically a value calculated by, for example, the following "Method for Measuring Gel Fraction".
[0229] Approximately 0.1 g of the adhesive layer is taken from the adhesive sheet, wrapped in a porous tetrafluoroethylene sheet with an average pore size of 0.2 μm (product name "NTF1122", manufactured by Nitto Denko Corporation), tied with kite string, and the weight at this point is measured. This weight is considered the weight before immersion. This weight before immersion is the total weight of the adhesive layer (the adhesive layer taken above), the tetrafluoroethylene sheet, and the kite string. The total weight of the tetrafluoroethylene sheet and the kite string is also measured and considered the weight of the package. Next, the adhesive layer, wrapped in a tetrafluoroethylene sheet and tied with kite string (referred to as the "sample"), is placed in a 50 ml container filled with ethyl acetate and left to stand at 23°C for 7 days. After that, the sample (after ethyl acetate treatment) is removed from the container, transferred to an aluminum cup, and dried in a drying oven at 130°C for 2 hours to remove the ethyl acetate. The weight is then measured and this weight is taken as the weight after immersion. Then, the gel fraction is calculated using the following formula. Gel fraction [% (weight %)] = (XY) / (ZY) × 100
[0230] The gel fraction can be adjusted, for example, by the type of adhesive polymer (A), the type and amount of adhesive segment (A), the monomer composition and amount, the type and amount of the ionic compound of the present invention, the type of conductive polymer (B), the type and amount of conductive segment (B), the monomer composition and amount, the type and amount of crosslinking agent, the ratio of adhesive polymer (A) to conductive polymer (B), the ratio of adhesive segment (A) to conductive segment (B), and the method for forming the sea-island structure described above.
[0231] The storage modulus of the adhesive layer of the present invention at 25°C and 1 Hz is not particularly limited, but is 3 × 10 4 It is preferable that the storage modulus of the adhesive layer of the present invention at 25°C and 1 Hz is 3 × 10⁻⁶. 4 A configuration with a storage modulus of Pa or higher is preferable in that it is less likely to cause dents during handling. In terms of suppressing dents in the adhesive layer of the present invention, the storage modulus of the adhesive layer of the present invention at 25°C and 1 Hz is 5 × 10⁻⁶. 4 Pa or higher is more preferable, 1 × 10 5It may be Pa or higher. The upper limit of the storage modulus of the adhesive layer of the present invention at 25°C and 1 Hz is not particularly limited, but from the viewpoint of the step-following ability of the adhesive layer of the present invention, 5 × 10 6 Preferably Pa or less, 1 × 10 6 Please refer to the following below Pa.
[0232] The storage modulus of the adhesive sheet of the present invention at 25°C and 1Hz can be measured by dynamic viscoelasticity measurement. The storage modulus of the adhesive sheet of the present invention at 25°C and 1Hz can be adjusted by the type of adhesive polymer (A), the type and amount of monomers of adhesive segments (A), the type and amount of the ionic compound of the present invention, the type of conductive polymer (B), the type and amount of monomers of conductive segments (B), the type and amount of crosslinking agent, the ratio of adhesive polymer (A) to conductive polymer (B), the ratio of adhesive segments (A) to conductive segments (B), and the method of forming the sea-island structure described above.
[0233] The thickness of the adhesive layer of the present invention is not particularly limited, but is preferably 5 to 250 μm, and more preferably 7 to 240 μm, 10 to 230 μm, 12 to 220 μm, 15 to 210 μm, 20 to 200 μm, 23 to 175 μm, or 25 to 150 μm. A thickness above a certain level is preferable because it improves step-following ability and adhesive reliability. Conversely, a thickness below a certain level is preferable because it is particularly excellent in terms of handling and manufacturability.
[0234] The method for producing the adhesive layer of the present invention is not particularly limited. For example, it can be produced by preparing the adhesive composition (precursor composition) of the present invention and, if necessary, irradiating it with active energy rays, heating and drying it, etc. Specifically, it can be produced by mixing an adhesive polymer (A), a conductive polymer (B), a mixture of monomer components constituting the conductive polymer (B) or a partially polymer thereof, or a block copolymer of the present invention, with additives as necessary.
[0235] The method for producing the adhesive layer of the present invention is not particularly limited, but examples include applying (coating) the above adhesive composition onto a substrate or release liner, and drying, curing, or drying and curing as necessary.
[0236] Furthermore, known coating methods may be used for applying (coating) the above adhesive composition. For example, coaters such as gravure roll coaters, reverse roll coaters, kiss roll coaters, dip roll coaters, bar coaters, knife coaters, spray coaters, comma coaters, and direct coaters may be used.
[0237] [3. Adhesive sheet] The adhesive sheet of the present invention is an adhesive layer formed by the adhesive composition of the present invention. The adhesive sheet of the present invention only needs to have the adhesive layer of the present invention (an adhesive layer formed by the adhesive composition of the present invention), and is not particularly limited in any other respect.
[0238] The adhesive sheet of the present invention may be a double-sided adhesive sheet in which both sides are adhesive layer surfaces, or a single-sided adhesive sheet in which only one side is an adhesive layer surface. In particular, a double-sided adhesive sheet is preferred from the viewpoint of bonding two members together. In this specification, the term "adhesive sheet" also includes tape-like materials, i.e., "adhesive tape." In this specification, the surface of the adhesive layer may be referred to as the "adhesive surface."
[0239] The adhesive sheet of the present invention may have a release liner on the adhesive surface until it is in use.
[0240] The adhesive sheet of the present invention may be a so-called "substrate-less type" adhesive sheet (hereinafter sometimes referred to as "substrate-less adhesive sheet") that does not have a base material (substrate layer), or it may be an adhesive sheet of the type that has a base material (hereinafter sometimes referred to as "adhesive sheet with base material"). Examples of the above-mentioned substrate-less adhesive sheet include a double-sided adhesive sheet consisting only of the above-mentioned adhesive layer, and a double-sided adhesive sheet consisting of the above-mentioned adhesive layer and an adhesive layer other than the above-mentioned adhesive layer (sometimes referred to as "other adhesive layer"). On the other hand, examples of the adhesive sheet with base material include an adhesive sheet having the above-mentioned adhesive layer on at least one side of the base material. Among these, the substrate-less adhesive sheet (substrate-less double-sided adhesive sheet) is preferred, and more preferably, the substrate-less double-sided adhesive sheet consisting only of the above-mentioned adhesive layer. Note that the above-mentioned "base material (substrate layer)" does not include a release liner that is peeled off when the adhesive sheet is used (applied). The adhesive sheet of the present invention is preferably a substrate-less adhesive sheet.
[0241] Figure 1 shows one embodiment of the adhesive sheet of the present invention (substrate-less adhesive sheet). In the adhesive sheet of Figure 1, 10 is the adhesive layer, and 11 and 12 are the release liners.
[0242] [3-1. Various physical properties of adhesive sheets] The 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 23°C (in particular, the 180° peel-off adhesive strength of the adhesive surface provided by the adhesive layer (the adhesive layer formed by the adhesive composition of the present invention) to the glass plate at 23°C) is not particularly limited, but from the viewpoint that sufficient adhesion can be obtained if the adhesive strength is high, it is preferably 4N / 20mm or higher, more preferably 6N / 20mm or higher, even more preferably 8N / 20mm or higher, and even more preferably 10N / 20mm or higher. If the 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 23°C is above a certain value, the adhesion to glass and the ability to suppress lifting at steps will be further improved. The upper limit of the 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 23°C is not particularly limited, but is preferably 28N / 20mm, 27N / 20mm, or 26N / 20mm, and more preferably 25N / 20mm, 24N / 20mm, 23N / 20mm, 22N / 20mm, 21N / 20mm, or 20N / 20mm.
[0243] The 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 80°C (particularly the 180° peel-off adhesive strength of the adhesive surface provided by the adhesive layer (the adhesive layer formed by the adhesive composition of the present invention) to the glass plate at 80°C) is not particularly limited, but from the viewpoint that sufficient adhesion can be obtained if the adhesive strength is high, it is preferably 4N / 20mm or more, more preferably 6N / 20mm or more, even more preferably 8N / 20mm or more, and even more preferably 10N / 20mm or more. If the 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 80°C is above a certain value, the adhesion to glass and the ability to suppress lifting at steps will be further improved. The upper limit of the 180° peel-off adhesive strength of the adhesive sheet of the present invention to a glass plate at 80°C is not particularly limited, but for example, 18N / 20mm is preferred, and more preferably 16N / 20mm. The 180° peel adhesion strength to the glass plate at 23°C or 80°C is determined by the 180° peel adhesion strength measurement method described below.
[0244] The glass plates mentioned above are not particularly limited, but examples include the product name "Soda-Lime Glass #0050" (manufactured by Matsunami Glass Industry Co., Ltd.). Other examples include alkali-free glass and chemically strengthened glass.
[0245] (A-1. Method for measuring 180° peel adhesion strength) The adhesive side of the adhesive sheet is attached to the substrate, and pressure is applied using a 2kg roller for one back-and-forth motion. The sheet is then aged for 30 minutes or 240 hours in an atmosphere of 23°C and 50%RH. After aging, the adhesive sheet is peeled off the substrate in accordance with JIS Z 0237, under conditions of 23°C or 80°C and 50%RH, at a tensile speed of 300mm / min and a peel angle of 180°. The 180° peel adhesion strength (N / 20mm) is then measured.
[0246] (B. Thickness) The thickness (total thickness) of the adhesive sheet of the present invention is not particularly limited, but is preferably 12 to 350 μm, and more preferably 15 to 330 μm, 18 to 325 μm, 18 to 320 μm, 20 to 300 μm, 23 to 300 μm, 25 to 275 μm, or 30 to 250 μm. A thickness above a certain level is preferable because it makes peeling at stepped areas less likely to occur. Also, a thickness below a certain level is preferable because it makes it easier to maintain an excellent appearance during manufacturing. Note that in the case of an adhesive sheet with a base material, the thickness of the base material is included in the thickness of the adhesive sheet of the present invention, but the thickness of the release liner is not included.
[0247] (C. Hayes) The haze of the adhesive sheet of the present invention (according to JIS K7136) is not particularly limited, but is preferably 3% or less, more preferably 1% or less, 0.7% or less, or 0.6% or less. A haze of 3% or less is preferable because it provides excellent transparency and a good appearance. The haze can be measured, for example, by leaving the adhesive sheet at room temperature (23°C, 50%RH) for at least 24 hours, peeling off the release liner if present, and attaching the sample to a glass slide (for example, one with a total light transmittance of 92% and a haze of 0.2%), using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., product name "HM-150N").
[0248] (D.Total light transmittance) The total light transmittance of the adhesive sheet of the present invention in the visible light wavelength range (according to JIS K7361-1) is not particularly limited, but is preferably 90% or higher, more preferably 91% or higher, or 92% or higher. A total light transmittance of 90% or higher is preferable because it provides excellent transparency and a good appearance. The total light transmittance can be measured, for example, by leaving the adhesive sheet at room temperature (23°C, 50%RH) for at least 24 hours, peeling off the release liner if one is present, and attaching the sample to a glass slide (for example, one with a total light transmittance of 92% and haze of 0.2%), using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., product name "HM-150N").
[0249] The adhesive strength, total light transmittance, and haze of the adhesive sheet of the present invention can be measured by the method described in the examples below. The adhesive strength, total light transmittance, and haze of the adhesive sheet of the present invention can be adjusted by adjusting the type, monomer composition and amount of the adhesive polymer (A) and adhesive segment (A), the type and amount of the ionic compound of the present invention, the type, monomer composition and amount of the conductive polymer (B) and conductive segment (B), the type and amount of the crosslinking agent, the ratio of adhesive polymer (A) to conductive polymer (B), the ratio of adhesive segment (A) to conductive segment (B), and the method of forming the sea-island structure described above.
[0250] [3-2. Method for manufacturing adhesive sheets] The adhesive sheet of the present invention is not particularly limited, but is preferably manufactured according to known or conventional manufacturing methods. For example, if the adhesive sheet of the present invention is a substrate-less adhesive sheet, it can be obtained by forming the adhesive layer on a release liner by the method described above. If the adhesive sheet of the present invention is a substrate-attached adhesive sheet, it can be obtained by directly forming the adhesive layer on the surface of the substrate (direct transfer method), or by first forming the adhesive layer on a release liner and then transferring (bonding) it to the substrate to provide the adhesive layer on the substrate (transfer method).
[0251] [3-3. Other layers of the adhesive sheet] The adhesive sheet of the present invention may have other layers in addition to the adhesive layer described above. Examples of other layers include other adhesive layers (adhesive layers other than the adhesive layer described above (adhesive layers other than the adhesive layer formed by the adhesive composition of the present invention)), intermediate layers, undercoat layers, etc. The adhesive sheet of the present invention may have two or more other layers.
[0252] [3-4. Substrate for adhesive sheets] When the adhesive sheet of the present invention is an adhesive sheet with a substrate, the substrate is not particularly limited, but examples include various optical films such as plastic films, anti-reflective (AR) films, polarizing plates, and phase difference plates. Examples of materials such as the plastic film include polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetylcellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymer, and cyclic olefin polymers such as the trade name "Arton (cyclic olefin polymer, manufactured by JSR Corporation)" and the trade name "Zeonor (cyclic olefin polymer, manufactured by Nippon Zeon Co., Ltd.)". These plastic materials may be used individually or in combination of two or more. Furthermore, the "substrate" mentioned above refers to the portion that is attached to the adherend together with the adhesive layer when the adhesive sheet is attached to the adherend. The release liner that is peeled off when the adhesive sheet is used (attached) is not included in the "substrate".
[0253] The above substrate is preferably transparent. The total light transmittance of the above substrate in the visible light wavelength range (according to JIS K7361-1) is not particularly limited, but is preferably 85% or more, and more preferably 88% or more. The haze of the above substrate (according to JIS K7136) is not particularly limited, but is preferably 1.0% or less, and more preferably 0.8% or less. Examples of such transparent substrates include PET film and non-oriented films such as the trade names "Arton" and "Zeonor".
[0254] The thickness of the above-mentioned substrate is not particularly limited, but is preferably, for example, 1 to 500 μm. The above-mentioned substrate may be in the form of a single layer or multiple layers. Furthermore, the surface of the above-mentioned substrate may be appropriately subjected to known and conventional surface treatments, such as physical treatments such as corona discharge treatment or plasma treatment, or chemical treatments such as undercoating.
[0255] [3-5. Adhesive sheet release liner] The adhesive sheet of the present invention may have a release liner on the adhesive surface until use. If the adhesive sheet of the present invention is a double-sided adhesive sheet, each adhesive surface may be protected by two release liners, or it may be protected by a single release liner with both sides being release surfaces, in a roll-like manner. The release liner is used as a protective material for the adhesive layer and is peeled off when it is applied to the substrate. Furthermore, if the adhesive sheet of the present invention is a substrate-less adhesive sheet, the release liner also serves as a support for the adhesive layer. Note that the release liner is not necessarily required.
[0256] As the above-mentioned release liner, conventional release paper can be used. Specifically, for example, in addition to a substrate having a release treatment layer with a release treatment agent on at least one surface, low-adhesion substrates made of fluorine-based polymers (e.g., polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, chlorofluoroethylene-vinylidene fluoride copolymer, etc.) or low-adhesion substrates made of non-polar polymers (e.g., polyethylene, polypropylene, and other olefin resins) can be used.
[0257] As the above-mentioned peel-off liner, for example, a peel-off liner having a release treatment layer formed on at least one surface of the peel-off liner substrate can be suitably used. Examples of such peel-off liner substrates include plastic substrate films (synthetic resin films) such as polyester film (polyethylene terephthalate film, etc.), olefin resin film (polyethylene film, polypropylene film, etc.), polyvinyl chloride film, polyimide film, polyamide film (nylon film), and rayon film, as well as paper (high-quality paper, Japanese paper, kraft paper, glassine paper, synthetic paper, topcoat paper, etc.), and composites of these made by laminating or co-extrusion (2-3 layer composites).
[0258] The release agent constituting the above-mentioned release layer is not particularly limited, but for example, silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, etc., can be used. The release agent can be used alone or in combination of two or more types.
[0259] The thickness of the release liner is not particularly limited and can be appropriately selected from the range of 5 to 100 μm.
[0260] The above-mentioned peel-off liner may have an antistatic layer formed on at least one surface of the substrate for the peel-off liner in order to prevent damage to the adherend such as an image display panel. The antistatic layer may be formed on one surface of the peel-off liner (the peel-off treated surface or the untreated surface), or on both surfaces of the peel-off liner (the peel-off treated surface and the untreated surface).
[0261] The antistatic layer is not particularly limited, but for example, it is an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer onto a peeling liner. Specifically, for example, it is an antistatic layer formed by coating a conductive coating liquid containing a conductive polymer onto a peeling liner (the peeled surface and / or the untreated surface). Specific coating methods include roll coating, bar coating, and gravure coating.
[0262] As the conductive polymer, polymers such as polyaniline-based, polythiophene-based, polypyrrole-based, and polyquinoxaline-based polymers can be used.
[0263] The thickness of the antistatic layer is preferably 1 nm to 1000 nm, and more preferably 5 nm to 900 nm. The antistatic layer may consist of only one layer or two or more layers.
[0264] [3-6. Uses of adhesive sheets, etc.] The adhesive sheet of the present invention has an adhesive layer (an adhesive layer formed by the adhesive composition of the present invention), and therefore exhibits excellent antistatic properties. For this reason, when used for bonding image display devices, display defects due to static electricity are less likely to occur. Accordingly, the adhesive layer formed from the adhesive composition of the present invention satisfies excellent antistatic properties, transparency, moisture and heat resistance, and low contamination properties, making it useful in the manufacture of image display devices.
[0265] Furthermore, the adhesive layer of the present invention exhibits excellent adhesion, foaming and peeling resistance, stress relaxation, step-following ability, adhesive reliability, and especially adhesive reliability at high temperatures. It also has excellent appearance. For these reasons, the adhesive sheet of the present invention is useful for adherends that are prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate resin (PMMA) may contain unreacted monomers, making it prone to foaming due to foreign matter at high temperatures. Polycarbonate (PC) is also prone to outgassing of water and carbon dioxide at high temperatures. Since the adhesive sheet of the present invention has excellent foaming and peeling resistance, it is also useful for plastic adherends containing such resins.
[0266] Furthermore, the adhesive sheet of the present invention can be useful not only for adherends with a low coefficient of thermal expansion, but also for adherends with a high coefficient of thermal expansion. The adherends with a low coefficient of thermal expansion are not particularly limited, but for example, glass plates (coefficient of thermal expansion: 0.3 × 10⁻⁶). -5 ~0.8 × 10 -5 ( / °C), polyethylene terephthalate substrate (PET film, coefficient of linear expansion: 1.5 × 10⁻⁶) -5 ~2×10 -5 Examples include ( / °C). Furthermore, the adherend with a large coefficient of linear expansion is not particularly limited, but examples include resin substrates with a large coefficient of linear expansion, and more specifically, polycarbonate resin substrates (PC, coefficient of linear expansion: 7 × 10⁻⁶). -5 ~8×10 -5 (°C), polymethyl methacrylate resin substrate (PMMA, coefficient of linear expansion: 7 × 10) -5 ~8×10 -5 ( / °C), cycloolefin polymer substrate (COP, coefficient of linear expansion: 6 × 10⁻⁶) -5 ~7×10-5 Examples include products such as "Zeonor" (manufactured by Nippon Zeon Co., Ltd.) and "Arton" (manufactured by JSR Corporation).
[0267] The adhesive sheet of the present invention is useful for bonding a substrate with a low coefficient of thermal expansion to a substrate with a high coefficient of thermal expansion. Specifically, the adhesive sheet of the present invention is preferably used for bonding a glass substrate (e.g., a glass plate, chemically strengthened glass, a glass lens, etc.) to a resin substrate with a high coefficient of thermal expansion.
[0268] Thus, the adhesive sheet of the present invention is useful for bonding various materials together, and is particularly useful for bonding glass substrates to plastic substrates. The plastic substrate may be an optical film, such as a plastic film having an ITO (indium tin oxide) layer on its surface.
[0269] Furthermore, the adhesive sheet of the present invention can be useful not only for adherends with smooth surfaces but also for adherends with steps on their surfaces. In particular, the adhesive sheet of the present invention can be useful for bonding a glass adherend to a resin substrate with a high coefficient of thermal expansion, even if at least one of the glass adherend or the resin substrate with a high coefficient of thermal expansion has steps on its surface.
[0270] The adhesive sheet of the present invention is preferably used in the manufacture of portable electronic devices. Examples of such portable electronic devices include mobile phones, PHS phones, smartphones, tablets (tablet computers), mobile computers (mobile PCs), personal digital assistants (PDAs), electronic organizers, portable broadcast receivers such as portable televisions and portable radios, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and camcorder-type video cameras.
[0271] The adhesive sheet of the present invention is preferably used, for example, for bonding components and modules that constitute portable electronic devices to each other, or for fixing components and modules that constitute portable electronic devices to the housing. More specifically, examples include bonding cover glass or lenses (especially glass lenses) to touch panels or touch sensors, fixing cover glass or lenses (especially glass lenses) to the housing, fixing display panels to the housing, fixing input devices such as sheet keyboards and touch panels to the housing, bonding protective panels of information display units to the housing, bonding housings to each other, bonding housings to decorative sheets, and fixing and bonding various components and modules that constitute portable electronic devices. In this specification, a display panel refers to a structure that is at least composed of a lens (especially a glass lens) and a touch panel. Furthermore, the term "lens" in this specification is a concept that includes both transparent materials that exhibit light refraction and transparent materials that do not exhibit light refraction. In other words, the term "lens" in this specification also includes simple window panels that do not exhibit light refraction.
[0272] Furthermore, the adhesive sheet of the present invention is preferably used in optical applications. That is, the adhesive sheet of the present invention is preferably an optical adhesive sheet used in optical applications. More specifically, it is preferably used, for example, in applications for bonding optical components (for bonding optical components) or in the manufacture of products using the optical components (optical products).
[0273] [4. Optical Components] This adhesive sheet can be suitably used for bonding optical components of the present invention. While the adhesive sheet may have a release liner on its adhesive surface until use, the adhesive sheet in the optical component of the present invention is an adhesive sheet used during use and therefore does not have a release liner.
[0274] An optical component refers to a component that possesses optical properties (for example, polarization, refractiveness, scattering, reflectivity, transmission, absorption, diffraction, optical rotation, visibility, etc.). The substrates constituting the optical components described above are not particularly limited, but examples include substrates constituting devices (optical instruments) such as display devices (image display devices) and input devices, or substrates used in such devices. Examples include polarizing plates, wave plates, phase difference plates, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coat films (films in which at least one side of a plastic film such as a PET film is hard-coated), transparent conductive films (for example, plastic films having an ITO layer on the surface (preferably ITO films such as PET-ITO, polycarbonate, or cycloolefin polymer)), decorative films, ornamental films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass sensors, glass display panels (LCDs, etc.), glass substrates such as glass plates with transparent electrodes, etc.), and even substrates on which these are laminated (these are sometimes collectively referred to as "functional films"). Furthermore, these films may have metal nanowire layers or conductive polymer layers. In addition, these films may have fine metal wires printed on them as a mesh. Furthermore, the terms "plate" and "film" above include forms such as plate-like, film-like, and sheet-like shapes, respectively. For example, "polarizing film" includes "polarizing plates" and "polarizing sheets," etc. Also, "film" includes film sensors, etc.
[0275] Examples of the above-mentioned display devices include liquid crystal displays, organic electroluminescent (EL) displays, PDPs (plasma display panels), and electronic paper. Examples of the above-mentioned input devices include touch panels.
[0276] The substrate constituting the optical component described above is not particularly limited, but examples include substrates made of glass, acrylic resin, polycarbonate, polyethylene terephthalate, cycloolefin polymer, metal thin film, etc. (for example, sheet-shaped, film-shaped, or plate-shaped substrates). In this invention, the term "optical component" also includes components that serve a decorative or protective role while maintaining the visibility of display devices and input devices (such as decorative films, surface protection films, etc.).
[0277] If the adhesive sheet of the present invention is an adhesive sheet with a base material, and the adhesive sheet constitutes a component having optical properties, then the base material can be considered equivalent to the substrate, and the adhesive sheet can be said to be an optical component of the present invention.
[0278] If the adhesive sheet of the present invention is an adhesive sheet with a base material, and the functional film described above is used as the base material, the adhesive sheet of the present invention can also be used as an "adhesive functional film" having the adhesive layer described above on at least one side of the functional film. [Examples]
[0279] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way by these examples.
[0280] Manufacturing Example 1 <Preparation of Acrylic Polymer Solution 1> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 81.8 parts by mass of butyl acrylate, 5.5 parts by mass of acrylic acid, 12.7 parts by mass of acryloylmorpholine (manufactured by KJ Chemicals), 0.75 parts by mass of trithiocarbonate-bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a RAFT agent, 0.047 parts by mass of 2,2'-azobis(2-methylpropionic acid)dimethyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (Step 1 of the RAFT polymerization reaction). This yielded acrylic polymer solution 1 containing acrylic polymer P1.
[0281] Example 1 <Preparation of Block Copolymer Solution 2> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 30 parts by mass (solid content) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 65 parts by mass of 2-methoxyethyl acrylate, 5 parts by mass of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (manufactured by Wako Pure Chemical Industries, Ltd.) as an ionic compound (ionic monomer), 0.020 parts by mass of 2,2'-azobis(2-methylpropionic acid)dimethyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (Step 2 of the RAFT polymerization reaction). This yielded block copolymer solution 2 containing block copolymer P2. Block copolymer P2 is an ABA-type triblock copolymer, where segment A is an adhesive segment derived from acrylic polymer P1, and segment B is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of Adhesive Composition 1> To the block copolymer solution 2 containing the block copolymer P2 obtained above, the following components were uniformly mixed per 100 parts by mass of block copolymer P2 (base polymer) to prepare adhesive composition 1. Crosslinking agent: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "Tetrad C", manufactured by Mitsubishi Gas Chemical Company): 0.05 parts by mass <Manufacturing of adhesive sheet 1> A release liner (polyester film, 38 μm thick, manufactured by Mitsubishi Chemical Corporation, MRF#38) with one side being a release surface was coated with the adhesive composition 1 obtained above to form a coating film. Next, this coating film was dried at 152°C for 3 minutes to form an adhesive layer with a thickness of 25 μm. A release liner (polyester film, 38 μm thick, manufactured by Mitsubishi Chemical Corporation, MRF#38) with one side being a release surface was laminated to this adhesive layer. After that, it was aged at 60°C for 1 day to allow the crosslinking reaction to proceed in the adhesive layer and to obtain an adhesive sheet 1.
[0282] Example 2 <Preparation of Block Copolymer Solution 3> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 20 parts by mass (solid content) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 75 parts by mass of 2-methoxyethyl acrylate, 5 parts by mass of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (manufactured by Wako Pure Chemical Industries, Ltd.) as an ionic compound (ionic monomer), 0.014 parts by mass of 2,2'-azobis(2-methylpropionic acid)dimethyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (Step 2 of the RAFT polymerization reaction). This yielded block copolymer solution 3 containing block copolymer P3. Block copolymer P3 is an ABA-type triblock copolymer, where segment A is an adhesive segment derived from acrylic polymer P1, and segment B is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of Adhesive Composition 2> Adhesive composition 2 was prepared in the same manner as in Example 1, except that block copolymer solution 3 containing the block copolymer P3 obtained above was used instead of block copolymer solution 2. <Manufacturing of adhesive sheet 2> Adhesive sheet 2 was prepared in the same manner as in Example 1, except that adhesive composition 2 obtained above was used instead of adhesive composition 1.
[0283] Example 3 <Preparation of Block Copolymer Solution 4> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 10 parts by mass (solid content) of acrylic polymer solution 1 containing acrylic polymer P1 obtained in Production Example 1, 85 parts by mass of 2-methoxyethyl acrylate, 5 parts by mass of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (manufactured by Wako Pure Chemical Industries, Ltd.) as an ionic compound (ionic monomer), 0.014 parts by mass of 2,2'-azobis(2-methylpropionic acid)dimethyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (Step 2 of the RAFT polymerization reaction). This yielded block copolymer solution 4 containing block copolymer P4. Block copolymer P4 is an ABA-type triblock copolymer, where segment A is an adhesive segment derived from acrylic polymer P1, and segment B is a conductive segment containing (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of Adhesive Composition 3> Adhesive composition 3 was prepared in the same manner as in Example 1, except that block copolymer solution 4 containing block copolymer P4 obtained above was used instead of block copolymer solution 2. <Manufacturing of adhesive sheet 3> Adhesive sheet 3 was prepared in the same manner as in Example 1, except that adhesive composition 3 obtained above was used instead of adhesive composition 1.
[0284] Comparative Example 1 <Preparation of Acrylic Polymer Solution 5> In a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 24.5 parts by mass of butyl acrylate, 1.7 parts by mass of acrylic acid, 3.8 parts by mass of acryloylmorpholine (manufactured by KJ Chemicals), 65 parts by mass of 2-methoxyethyl acrylate, 5 parts by mass of (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide (manufactured by Wako Pure Chemical Industries, Ltd.), 0.25 parts by mass of trithiocarbonate=bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a RAFT agent, 0.023 parts by mass of 2,2'-azobis(2-methylpropionic acid)dimethyl (manufactured by Wako Pure Chemical Industries, Ltd.) as a polymerization initiator, and 100 parts by mass of ethyl acetate as a solvent was stirred at 75°C for 6 hours under a nitrogen atmosphere (Step 1 of the RAFT polymerization reaction). This yielded an acrylic polymer solution 5 containing acrylic polymer P5. Acrylic polymer P5 is not a block copolymer, but a conductive polymer containing (2-acryloyloxyethyl)trimethylammonium=bis(trifluoromethanesulfonyl)imide as a monomer unit. <Preparation of Adhesive Composition 4> Adhesive composition 4 was prepared in the same manner as in Example 1, except that the acrylic polymer solution 5 obtained above was used instead of block copolymer solution 1. <Manufacturing of adhesive sheet 4> An adhesive sheet 4 was prepared in the same manner as in Example 1, except that adhesive composition 4 containing the acrylic polymer P5 obtained above was used instead of adhesive composition 1.
[0285] The adhesive sheets obtained in Examples 1-3 and Comparative Example 1 were used for the following evaluations. The results are shown in Table 2.
[0286] <Measurement of surface resistance> After peeling off one of the release liners from the adhesive sheets obtained in the examples and comparative examples, the surface resistance of the adhesive layer surface was measured. The measurement was performed using an MCP-HT450 manufactured by Mitsubishi Chemical Analytec Co., Ltd. under an atmosphere of 23°C and 50% RH.
[0287] <Presence or absence of microphase separation structure> The presence or absence of a microphase separation structure was confirmed in the adhesive layer of each adhesive sheet obtained in the examples and comparative examples as follows. First, samples for observation by transmission electron microscopy (TEM) were prepared. Specifically, the adhesive layer was stained and then rapidly frozen, and a thin section was cut from the adhesive layer using an ultramicrotome (Leica). Then, the thin section was observed and photographed using a transmission electron microscope (product name "HT7820", Hitachi High-Technologies Corporation). Next, the presence or absence of phase separation was confirmed by analyzing the obtained TEM images using image analysis software and binarizing them.
[0288] [Table 2]
[0289] Despite containing the same 5% by weight of ionic monomer in the adhesive layers of Examples 1-3 and Comparative Example 1, the surface resistance of the adhesive layers of Examples 1-3 is approximately half or less that of Comparative Example 1. Therefore, it is considered that the ionic monomer is more unevenly distributed in the continuous phase (sea area) than in the discontinuous phase (island area) of the phase-separated adhesive layers of Examples 1-3, efficiently forming conductive paths.
[0290] Variations of the present invention are listed below. [Note 1] Contains two or more polymers and an ionic compound, At least one of the two or more polymers mentioned above includes an adhesive polymer (A), It has a sea-island structure that is divided into a continuous phase and a discontinuous phase. The continuous phase (sea portion) is an adhesive composition containing the ionic compound. [Note 2] The discontinuous phase (island portion) is the adhesive composition according to Note 1, comprising the adhesive polymer (A). [Note 3] The discontinuous phase (island portion) is the adhesive composition according to Note 1 or 2, comprising the ionic compound. [Note 4] The ionic compound is an adhesive composition according to any one of Notes 1 to 3, including an organic compound. [Note 5] The adhesive composition according to any one of Notes 1 to 4, wherein at least one of the two or more polymers is a conductive polymer (B) that forms a covalent bond with the ionic compound. [Note 6] The adhesive composition according to Note 5, wherein the weight ratio of the conductive polymer (B) to the adhesive polymer (A) (conductive polymer (B) / adhesive polymer (A)) is 10 / 90 to 99 / 1. [Note 7] The adhesive composition according to Note 5 or 6, wherein the adhesive polymer (A) and the conductive polymer (B) form a block copolymer. [Note 8] An adhesive layer formed by the adhesive composition described in any one of Notes 1 to 7. [Note 9] An adhesive sheet having the adhesive layer described in Note 8. [Note 10] The adhesive sheet described in Note 9, having a thickness of 12 to 350 μm. [Explanation of Symbols]
[0291] 1 Adhesive sheet 10 Adhesive layer 11, 12 Peel-off liner
Claims
1. The composition includes two or more polymers and an ionic compound, At least one of the two or more polymers contains an adhesive polymer (A), It has a sea-island structure in which a continuous phase and a discontinuous phase are separated, The continuous phase (sea portion) of the pressure-sensitive adhesive composition contains the ionic compound.
2. The pressure-sensitive adhesive composition according to claim 1 , wherein the discontinuous phase (island portion) contains the adhesive polymer (A).
3. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the discontinuous phase (island portion) contains the ionic compound.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the ionic compound includes an organic compound.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein at least one of the two or more polymers comprises a conductive polymer (B) that forms a covalent bond with the ionic compound.
6. The pressure-sensitive adhesive composition according to claim 5, wherein the weight ratio of the conductive polymer (B) to the adhesive polymer (A) (conductive polymer (B) / adhesive polymer (A)) is 10 / 90 to 99 / 1.
7. The pressure-sensitive adhesive composition according to claim 5 or 6, wherein the pressure-sensitive adhesive polymer (A) and the conductive polymer (B) form a block copolymer.
8. A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 7.
9. A pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer according to claim 8.
10. The pressure-sensitive adhesive sheet according to claim 9, having a thickness of 12 to 350 μm.